Composition, film and optical sensor

By using high reflectivity particles with particle size less than 200 nm and specific film forming components, a film with high light scattering performance and good storage stability is formed, and the problem of insufficient stability of the light scattering film in the prior art is solved.

JP7667735B2Active Publication Date: 2025-04-23FUJIFILM CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021526955
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-27
Filing Date
2020-06-22
Publication Date
2025-04-23
Estimated Expiration
2040-06-22

AI Technical Summary

Technical Problem

The prior art is difficult to achieve good storage stability of the film while maintaining high light scattering performance, especially due to the sedimentation problem caused by the heavy degree of high reflectivity particles.

Method used

Using high reflectivity particles (reflectivity 2.0 or above) with a particle size less than 200 nm and a combination of at least one type of film forming component, the film forming component includes a resin and an overcompound, and a solvent, a 4-micron thick film is formed by heat treatment, and the film has a maximum light transmission mittance and phase separation structure of less than 80%.

Benefits of technology

Good storage stability and high light scattering performance of the film are achieved, and the light scattering efficiency and angle dependence are optimized through the phase separation structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667735000055
    Figure 0007667735000055
  • Figure 0007667735000056
    Figure 0007667735000056
  • Figure 0007667735000001
    Figure 0007667735000001
Patent Text Reader

Abstract

Provided is a composition comprising: particles having a refractive index of at least 2.0 and an average primary particle diameter of at most 200 nm; a film-forming component including at least one selected from a resin and a polymerizable monomer; and a solvent, wherein the film-forming component includes at least two kinds of resins, or includes at least one kind of resin and at least one kind of polymerizable monomer, and when a film having a thickness of 4 μm is formed by heating said composition at 200°C for 5 minutes, the maximum value of light transmittance in the wavelength range of 400-1000 nm of the film is at most 80%, and the film has therein a phase-separated structure in which a first phase including the particles and a second phase having a lower particle content than the first phase are separated. Also provided are a film and an optical sensor in which said composition is used.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to compositions, films, and optical sensors that include high refractive index particles. [Background technology]

[0002] Titanium oxide is a particle with a high refractive index. Attempts to use such particles with a high refractive index for light scattering films and the like are being considered.

[0003] Patent Document 1 describes an invention relating to a light-scattering sheet including a light-scattering layer that includes a plurality of polymers having different refractive indices from one another and has a bicontinuous phase structure in at least a portion of the region, which transmits and scatters incident light isotropically, has a scattering angle showing a maximum value of the scattered light intensity of 2 to 40°, and has a total light transmittance of 70 to 100%. Any of the continuous phases that form the bicontinuous phase structure may include highly refractive fine particles. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2016-161859 A Summary of the Invention [Problem to be solved by the invention]

[0005] In recent years, there has been an increasing demand for films that moderately block visible light and have high light scattering properties. In order to increase the light scattering properties of a film, a method is known in which particles with a large particle size and a high refractive index are used. However, particles with a high refractive index (hereinafter also referred to as high refractive particles) generally tend to have a high specific gravity. When such particles with a high specific gravity are used by being contained in a composition containing a solvent, the particles may settle during storage of the composition. For this reason, it has been difficult for conventionally known compositions to achieve both high storage stability and high light scattering properties of the resulting film.

[0006] In addition, since the light-scattering sheet of the invention described in Patent Document 1 is said to have a total light transmittance of 70 to 100%, the light-scattering sheet of the invention described in Patent Document 1 is not a material that moderately blocks visible light, but rather has high visible light transmittance.

[0007] Accordingly, an object of the present invention is to provide a composition capable of forming a film having good storage stability and excellent light scattering properties, and also to provide the film and an optical sensor. [Means for solving the problem]

[0008] Under such circumstances, the present inventors have conducted extensive research and have found that the above object can be achieved by the composition described below, which has led to the completion of the present invention. <1> A composition comprising particles having a refractive index of 2.0 or more and an average primary particle size of 200 nm or less, a film-forming component including at least one selected from a resin and a polymerizable monomer, and a solvent, The film-forming component includes two or more resins, or includes one or more resins and one or more polymerizable monomers; When the composition is used to form a film having a thickness of 4 μm by heating at 200° C. for 5 minutes, the maximum transmittance of the film in the wavelength range of 400 to 700 nm is 80% or less, and the film has a phase-separated structure including a first phase containing the particles and a second phase having a smaller content of the particles than the first phase. composition. <2> The film-forming component includes a resin as a dispersant for the particles and a resin as a binder. <1> The composition described in <3> The film-forming component includes two or more resins selected from a resin A1 having a structure in which a polymer chain is bonded to a trivalent or higher linking group and a resin A2 having a repeating unit having a graft chain, <1> or <2> The composition described in <4> The film-forming component is The resin A1-1 has a structure in which a polymer chain is bonded to a trivalent or higher linking group, and the resin A1-2 has a structure in which a polymer chain containing a repeating unit having a structure different from that of the polymer chain of the resin A1-1 is bonded to a trivalent or higher linking group, The resin A2-1 has a repeating unit having a graft chain, and the resin A2-2 has a repeating unit having a graft chain that includes a repeating unit having a structure different from that of the graft chain of the resin A2-1, or The resin A2-3 includes a repeating unit having a graft chain including a repeating unit having a structure different from that of the polymer chain of the resin A1-3. <3> The composition described in <5> The film-forming component includes at least one selected from a resin having a structure in which a polymer chain containing a repeating unit of a polyester structure is bonded to a trivalent or higher linking group and a resin having a repeating unit having a graft chain containing a repeating unit of a polyester structure, <1> ~ <4> 13. The composition according to any one of claims 1 to 12. <6> The film-forming component includes a polymerizable monomer containing a ring structure, <1> ~ <5> 13. The composition according to any one of claims 1 to 12. <7> The binder resin is contained in an amount of 40 to 250 parts by mass relative to 100 parts by mass of the resin serving as a dispersant for the particles. <2> The composition described in <8> The particles are inorganic particles. <1> ~ <7> 13. The composition according to any one of claims 1 to 12. <9> The average primary particle size of the particles is 100 nm or less. <1> ~ <8> 13. The composition according to any one of claims 1 to 12. <10> Contains two or more of the above particles, <1> ~ <9> 13. The composition according to any one of claims 1 to 12. <11> <1> ~ <10> A film obtained by using the composition according to any one of the above. <12> <11> An optical sensor comprising the film according to claim 1. Effect of the Invention

[0009] According to the present invention, it is possible to provide a composition capable of forming a film having good storage stability and excellent light scattering properties, and also to provide a film and an optical sensor. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic diagram illustrating an embodiment of an optical sensor of the present invention. [Diagram 2] FIG. 4 is a schematic diagram illustrating another embodiment of the optical sensor of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in detail below. The following description of the components may be based on representative embodiments of the present invention, but the present invention is not limited to such embodiments. In this specification, a numerical range expressed using "to" means a range that includes the numerical values ​​before and after "to" as the lower and upper limits. In the description of groups (atomic groups) in this specification, when no notation is given of substituted or unsubstituted, it includes both unsubstituted groups (atomic groups) and substituted groups (atomic groups). For example, an "alkyl group" includes not only unsubstituted alkyl groups (unsubstituted alkyl groups) but also substituted alkyl groups (substituted alkyl groups). In this specification, "(meth)acrylate" refers to acrylate and methacrylate, "(meth)acrylic" refers to acrylic and methacrylic, "(meth)allyl" refers to allyl and methallyl, and "(meth)acryloyl" refers to acryloyl and methacryloyl. In this specification, in the chemical formulae, Me represents a methyl group, Et represents an ethyl group, Pr represents a propyl group, Bu represents a butyl group, and Ph represents a phenyl group. In this specification, unless otherwise specified, the term "exposure" includes not only exposure using light but also drawing using particle beams such as electron beams and ion beams. Examples of light used for exposure include the bright line spectrum of a mercury lamp, far ultraviolet light represented by an excimer laser, extreme ultraviolet light (EUV light), X-rays, and actinic rays or radiation such as electron beams. In this specification, the weight average molecular weight and the number average molecular weight are defined as values ​​measured in terms of polystyrene by gel permeation chromatography (GPC). In this specification, the weight average molecular weight (Mw) and the number average molecular weight (Mn) can be determined, for example, by using HLC-8220GPC (manufactured by Tosoh Corporation), a column in which TOSOH TSKgel Super HZM-H, TOSOH TSKgel Super HZ4000 and TOSOH TSKgel Super HZ2000 are connected as columns, and tetrahydrofuran is used as a developing solvent. In this specification, unless otherwise specified, the refractive index value is the refractive index value for light with a wavelength of 589 nm at 23°C.

[0012] <Composition> The composition of the present invention is a composition comprising particles having a refractive index of 2.0 or more and an average primary particle size of 200 nm or less, a film-forming component including at least one selected from a resin and a polymerizable monomer, and a solvent, The film-forming component includes two or more resins, or includes one or more resins and one or more polymerizable monomers; When the composition is used to form a film having a thickness of 4 μm by heating at 200° C. for 5 minutes, the maximum transmittance of the film in the wavelength range of 400 to 700 nm is 80% or less, and the film has a phase-separated structure consisting of a first phase containing the particles and a second phase having a lower content of the particles than the first phase.

[0013] The composition of the present invention has good storage stability. That is, particles having a refractive index of 2.0 or more generally have a large specific gravity, but the composition of the present invention uses particles having a relatively small particle diameter of 200 nm or less as the particles having a refractive index of 2.0 or more, so that the sedimentation of the particles in the composition containing a solvent can be suppressed, and as a result, excellent storage stability can be obtained. In addition, the composition of the present invention has a characteristic that when a film having a thickness of 4 μm is formed by heating at 200 ° C. for 5 minutes, the maximum value of the transmittance of light in the wavelength range of 400 to 700 nm is 80% or less, and the film has a phase separation structure formed of a first phase containing the particles and a second phase having a lower content of the particles than the first phase. Since such a phase separation structure is formed in the film, when light is irradiated to a film obtained by using this composition, scattering occurs between the first phase having a relatively high content of the particles and the second phase having a relatively low content of the particles, and the light irradiated to the film can be efficiently scattered and transmitted. Therefore, a film having excellent light scattering properties can be formed by using the composition of the present invention. Furthermore, the angle dependency of scattered light can be reduced.

[0014] The base material of the first phase and the second phase is a film-forming component or a cured product derived from the film-forming component. The simple aggregate of the particles is one form of the particles, and the simple aggregate of the particles itself is not the first phase. The first phase is the film-forming component or the cured product derived from the film-forming component in which the particles are present. The second phase may have a lower content of the particles than the first phase, and may not substantially contain the particles. It is preferable that the second phase does not substantially contain the particles because it is easier to obtain better light scattering properties.

[0015] The formation of a phase-separated structure of the first phase and the second phase in the film can be observed using a scanning electron microscope (SEM), a transmission electron microscope (TEM), or an optical microscope. For example, the composition is applied to a support such as a glass substrate, heated at 200°C for 5 minutes to form a film with a thickness of 4 μm, and then the cross section of the obtained film in the thickness direction is observed using a scanning electron microscope (SEM), a transmission electron microscope (TEM), or an optical microscope to check whether a phase-separated structure of the first phase and the second phase is formed in the film.

[0016] The phase separation structure can be formed by appropriately changing the types of resin and polymerizable monomer used in the film-forming components.

[0017] In one embodiment, a method is used in which a film-forming component contains a first resin and a second resin having low compatibility with the first resin. When such a film-forming component is used, a phase separation structure can be formed during film formation between a phase containing the first resin as a main component and a phase containing the second resin as a main component. For example, when one of the first resin and the second resin is a resin serving as a dispersant for particles and the other is a binder resin, the phase containing the resin serving as a dispersant as a main component can have a large amount of particles unevenly distributed.

[0018] In another embodiment, a method is used in which a film-forming component containing a first resin and a polymerizable monomer having low compatibility with the first resin is used. When such a film-forming component is used, a phase-separated structure can be formed during film formation, with a phase containing the first resin as a main component and a phase containing a cured product derived from the polymerizable monomer as a main component.

[0019] In another embodiment, the types of resins and polymerizable monomers used in the film-forming components are appropriately changed, and the film-forming components are subjected to spinodal decomposition during film formation to form a phase-separated structure having a first phase and a second phase.

[0020] The phase separation structure in the film is preferably such that the phase interface is isotropically present in the film, and is more preferably, for example, a sea-island structure or a bicontinuous phase structure. By forming these phase separation structures, light can be effectively scattered between the first phase and the second phase, and particularly excellent light scattering properties are easily obtained. The sea-island structure is a structure formed by a sea region, which is a continuous region, and an island region, which is a discontinuous region. In the sea-island structure, the second phase may be a sea and the first phase may form islands, or the first phase may be a sea and the second phase may form islands. When the first phase is a sea and the second phase forms islands, it is preferable from the viewpoint of transmittance. When the first phase is an island and the second phase forms a sea, it is preferable from the viewpoint of angle dependency. In addition, the bicontinuous phase structure is a network structure in which the first phase and the second phase each form a continuous phase structure in an interpenetrating manner.

[0021] When the composition of the present invention is used to form a film having a thickness of 4 μm by heating at 200° C. for 5 minutes, the maximum transmittance of the film for light having a wavelength in the range of 400 to 700 nm is preferably 70% or less, more preferably 60% or less, and even more preferably 50% or less, from the viewpoint of reducing the wavelength dependency of light scattering. The lower limit of the maximum transmittance is preferably 1% or more, more preferably 5% or more, and even more preferably 10% or more. The maximum transmittance of the film for light of 400 to 1000 nm is preferably 80% or less, more preferably 70% or less, even more preferably 60% or less, and particularly preferably 50% or less. The lower limit of the maximum transmittance is preferably 1% or more, more preferably 5% or more, and even more preferably 10% or more.

[0022] The average interphase refractive index difference in the film is preferably 0.1 or more, more preferably 0.2 or more, even more preferably 0.3 or more, and particularly preferably 0.4 or more.

[0023] The haze of the film according to JIS K 7136 is preferably 30 to 100%. The upper limit is preferably 99% or less, more preferably 95% or less, and even more preferably 90% or less. The lower limit is preferably 35% or more, more preferably 40% or more, and even more preferably 50% or more.

[0024] A film having such spectral characteristics can be formed by appropriately adjusting the shape of the phase separation structure, the refractive index of the particles, the amount and uneven distribution of the particles in the film, etc. In this case, the higher the refractive index of the particles, the amount and uneven distribution of the particles, the better.

[0025] The solid content concentration of the composition of the present invention is preferably 5 to 80% by mass because better storage stability is easily obtained. The upper limit is preferably 75% by mass or less, more preferably 70% by mass or less. The lower limit is preferably 10% by mass or more, more preferably 15% by mass or more, and even more preferably 20% by mass or more. Each component used in the composition of the present invention will be described below.

[0026] <<Particle P1 (particles with a refractive index of 2.0 or more and an average primary particle size of 200 nm or less)>> The composition of the present invention contains particles (hereinafter also referred to as particles P1) having a refractive index of 2.0 or more and an average primary particle size of 200 nm or less.

[0027] The average primary particle diameter of the particles P1 is 200 nm or less, and preferably 100 nm or less from the viewpoint of the storage stability of the composition. Also, the average primary particle diameter of the particles P1 is preferably 5 nm or more and 100 nm or less from the viewpoint of the storage stability of the composition and the light scattering property of the obtained film, more preferably 10 nm or more and 100 nm or less, even more preferably 20 nm or more and 100 nm or less, even more preferably 30 nm or more and 100 nm or less, even more preferably 40 nm or more and 100 nm or less, and particularly preferably 50 nm or more and 100 nm or less.

[0028] In this specification, the average primary particle diameter of the particles is a value measured by the following method. That is, the primary particle diameter of the particles can be obtained by observing the particles with a transmission electron microscope (TEM) and observing the part (primary particle) where the particles are not aggregated. The particle size distribution of the particles can be obtained by taking a transmission electron micrograph of the primary particles with a transmission electron microscope, and then measuring the particle size distribution using the photograph with an image processing device. In this specification, the average primary particle diameter of the particles is the arithmetic mean diameter based on the number calculated from the particle size distribution. In this specification, an electron microscope (H-7000) manufactured by Hitachi, Ltd. is used as the transmission electron microscope, and Luzex AP manufactured by Nireco Corporation is used as the image processing device.

[0029] The refractive index of the particles P1 is 2.0 or more, preferably 2.2 or more, and more preferably 2.4 or more. The upper limit of the refractive index of the particles P1 is not particularly limited, but may be 5 or less, or may be 4 or less.

[0030] In this specification, the refractive index of the particles is a value measured by the following method. First, a dispersion is prepared using particles, a resin (dispersant) with a known refractive index, and propylene glycol monomethyl ether acetate. Then, the prepared dispersion is mixed with a resin with a known refractive index to prepare coating solutions with particle concentrations of 10 mass%, 20 mass%, 30 mass%, and 40 mass% in the total solid content of the coating solution. After these coating solutions are formed into a film with a thickness of 300 nm on a silicon wafer, the refractive index of the obtained film is measured using ellipsometry (Lambda Ace RE-3300, manufactured by SCREEN Holdings Co., Ltd.). Then, the refractive index corresponding to the particle concentration is plotted on a graph to derive the refractive index of the particles.

[0031] The specific gravity of particle P1 is 1 to 7 g / cm 3 The upper limit is preferably 6 g / cm 3 It is preferable that the density is less than 5 g / cm 3 The lower limit of the specific gravity is not particularly limited, but is preferably 1.5 g / cm 3Can be more than 2g / cm 3 It can be more than that.

[0032] In this specification, the specific gravity of particles is a value measured by the following method. First, 50 g of particles are placed in a 100 mL measuring flask. Next, 100 mL of water is measured using another 100 mL measuring cylinder. After that, the measured water is placed in the measuring flask to the extent that the particles are immersed, and then ultrasonic waves are applied to the measuring flask to mix the particles with the water. After that, additional water is added until the mark on the measuring flask is reached, and the specific gravity is calculated as 50 g / (volume of water remaining in the measuring flask) = specific gravity.

[0033] The particles P1 are preferably transparent or white particles. The particles P1 are preferably inorganic particles. Examples of the types of inorganic particles include titanium oxide particles, strontium titanate particles, barium titanate particles, zinc oxide particles, magnesium oxide particles, zirconium oxide particles, aluminum oxide particles, barium sulfate particles, and zinc sulfide particles. The inorganic particles used as the particles P1 are preferably particles having titanium atoms, and more preferably titanium oxide particles.

[0034] Titanium oxide particles are titanium dioxide (TiO 2 The titanium oxide particles preferably have a Ti content (purity) of 70% by mass or more, more preferably 80% by mass or more, and even more preferably 85% by mass or more. n O 2n-1 (n is an integer from 2 to 4), the content of low-order titanium oxide, titanium oxynitride, etc. is preferably 30 mass % or less, more preferably 20 mass % or less, and further preferably 15 mass % or less.

[0035] The titanium oxide may be rutile type titanium oxide or anatase type titanium oxide. From the viewpoint of coloring property and stability over time of the dispersion liquid or composition, rutile type titanium oxide is preferred. In particular, rutile type titanium oxide has little change in color difference even when heated, and has good coloring property. In addition, the rutile content of titanium oxide is preferably 95% or more, more preferably 99% or more.

[0036] Rutile titanium oxide can be a known one. There are two types of methods for producing rutile titanium oxide: a sulfuric acid method and a chlorine method. Titanium oxide produced by either method can be suitably used. Here, the sulfuric acid method refers to a method of producing titanium oxide by using ilmenite ore or titanium slag as a raw material, dissolving it in concentrated sulfuric acid to separate the iron content as iron sulfate, hydrolyzing the separated solution to obtain hydroxide precipitates, and firing them at high temperature to extract rutile titanium oxide. The chlorine method refers to a method of producing titanium oxide by using synthetic rutile or natural rutile as a raw material, reacting it with chlorine gas and carbon at a high temperature of about 1000°C to synthesize titanium tetrachloride, and oxidizing it to extract rutile titanium oxide. Rutile titanium oxide obtained by the chlorine method is preferable as the rutile titanium oxide.

[0037] The specific surface area of ​​titanium oxide particles is 10 to 400 m2 as measured by the BET (Brunauer, Emmett, Teller) method. 2 / g, and 10 to 200m 2 / g is more preferable, and 10 to 150m 2 More preferably, the range is 10 to 40 m / g. 2 / g is particularly preferred, and 10 to 20m 2 / g is most preferable. The pH of titanium oxide is preferably 6 to 8. The oil absorption of titanium oxide is preferably 10 to 60 (g / 100g), and more preferably 10 to 40 (g / 100g).

[0038] Titanium oxide particles are Fe 2 O 3 , Al 2 O 3 , SiO 2 , Nb2 O 5 and Na 2 The total amount of O is preferably 0.1 mass % or less, more preferably 0.05 mass % or less, further preferably 0.02 mass % or less, and particularly preferably substantially free of these.

[0039] The shape of the titanium oxide particles is not particularly limited. For example, the shape may be isotropic (e.g., spherical, polyhedral, etc.), anisotropic (e.g., needle, rod, plate, etc.), or amorphous. The hardness (Mohs hardness) of the titanium oxide particles is preferably 5 to 8, and more preferably 7 to 7.5.

[0040] Inorganic particles such as titanium oxide particles may be surface-treated with a surface treatment agent such as an organic compound. Examples of surface treatment agents used for the surface treatment of titanium oxide include polyols, aluminum oxide, aluminum hydroxide, silica (silicon oxide), hydrated silica, alkanolamines, stearic acid, organosiloxanes, zirconium oxide, hydrogen dimethicone, silane coupling agents, and titanate coupling agents. Among these, silane coupling agents are preferred. The surface treatment may be performed using one type of surface treatment agent alone, or two or more types of surface treatment agents in combination.

[0041] It is also preferred that inorganic particles such as titanium oxide particles are coated with a basic metal oxide or basic metal hydroxide, such as a metal compound containing magnesium, zirconium, cerium, strontium, antimony, barium, calcium, or the like.

[0042] As the titanium oxide particles, those described in "Titanium Oxide: Physical Properties and Application Technology, by Seino Manabu, pages 13-45, published on June 25, 1991, by Gihodo Publishing" can also be suitably used.

[0043] Commercially available particles P1 can be preferably used. Commercially available products may be used as they are, or may be classified before use. Commercially available titanium oxide particles include, for example, Typepaque R-550, R-580, R-630, R-670, R-680, R-780, R-780-2, R-820, R-830, R-850, R-855, R-930, R-980, CR-50, CR-50-2, CR-57, CR-58, CR-58-2, CR-60, CR-60-2, CR-63, CR-67, CR-Super70, CR-80, CR-85, and CR-90, both manufactured by Ishihara Sangyo Kaisha, Ltd. , CR-90-2, CR-93, CR-95, CR-953, CR-97, PF-736, PF-737, PF-742, PF-690, PF-691, PF-711, PF-739, PF-740, PC-3, S-305, C R-EL, PT-301, PT-401M, PT-401L, PT-501A, PT-501R, UT771, TTO-51, TTO-80A, TTO-S-2, A-220, MPT-136, MPT-140, MPT-141; Trade names of Sakai Chemical Industry Co., Ltd. include R-3L, R-5N, R-7E, R-11P, R-21, R-25, R-32, R-42, R-44, R-45M, R-62N, R-310, R-650, SR-1, D-918, GTR-100, FTR-700, TCR-52, A-110, A-190, SA-1, SA-1L, STR-100A-LP, STR-100C-LP, and TCA-123E; Product names manufactured by Teika Corporation: JR, JRNC, JR-301, JR-403, JR-405, JR-600A, JR-600E, JR-603, JR-605, JR-701, JR-800, JR-805, JR-806, JR-1000, MT-01, MT-05, MT-10EX, MT-100S, MT-100TV, MT -100Z, MT-100AQ, MT-100WP, MT-100SA, MT-100HD, MT-150EX, MT-150W, MT-300HD, MT-5 00B, MT-500SA, MT-500HD, MT-600B, MT-600SA, MT-700B, MT-700BS, MT-700HD, MT-700Z; Titan Kogyo Co., Ltd.'s product names: KR-310, KR-380, KR-380N, ST-485SA15; Product names: TR-600, TR-700, TR-750, TR-840, TR-900 manufactured by Fuji Titanium Industries Co., Ltd. An example of such a titanium oxide is Brilliant 1500, a product name of Shiraishi Calcium Co., Ltd. In addition, titanium oxide particles described in paragraphs 0025 to 0027 of JP2015-067794A can also be used.

[0044] Commercially available strontium titanate particles include SW-100 (manufactured by Titan Kogyo Co., Ltd.). Commercially available barium sulfate particles include BF-1L (manufactured by Sakai Chemical Industry Co., Ltd.). Commercially available zinc oxide particles include Zincox Super F-1 (manufactured by Hakusui Tech Co., Ltd.). Commercially available zirconium oxide particles include Z-NX (manufactured by Taiyo Koko Co., Ltd.) and Zirconeo-Cp (manufactured by Aitec Co., Ltd.).

[0045] The content of the particles P1 is preferably 5 to 90% by mass of the total solid content of the composition. The upper limit is preferably 85% by mass or less, more preferably 80% by mass or less, and even more preferably 70% by mass or less. The lower limit is preferably 6% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more.

[0046] The composition of the present invention may contain only one type of particle P1, or may contain two or more types. When only one type of particle P1 is contained, better storage stability is likely to be obtained. When two or more types of particle P1 are contained, the angle dependency of light scattering can be further reduced. When two or more types of particle P1 are contained, the total amount thereof is preferably within the above range.

[0047] <<Particle P2>> The composition of the present invention may contain particles (hereinafter also referred to as particles P2) having a refractive index of less than 2.0, an average primary particle diameter of 500 nm or more, and a specific gravity smaller than that of particles P1. When the composition of the present invention contains P2 in addition to P1, scattering occurs between particles P1 and P2, and light irradiated to the film can be efficiently scattered and transmitted. Therefore, by using such a composition, a film with excellent light scattering properties can be formed.

[0048] The average primary particle diameter of the particles P2 is 500 nm or more, preferably 500 nm or more and 6000 nm or less, more preferably 500 nm or more and 5000 nm or less, even more preferably 500 nm or more and less than 3000 nm, even more preferably 500 nm or more and 2500 nm or less, even more preferably 500 nm or more and 2000 nm or less, particularly preferably 500 nm or more and 1500 nm or less, and most preferably 500 nm or more and 1000 nm or less.

[0049] The refractive index of the particles P2 is less than 2.0, preferably 1.9 or less, more preferably 1.8 or less, and particularly preferably 1.7 or less. The lower limit of the refractive index of the particles P2 is not particularly limited, but may be 1.0 or more, or may be 1.1 or more.

[0050] The difference between the refractive index of the particle P1 and the refractive index of the particle P2 is preferably 0.5 or more, more preferably 0.7 or more, and even more preferably 0.9 or more, because it is easy to obtain a film with excellent light scattering properties. When the composition of the present invention contains two or more types of particle P1, the refractive index of the particle P1 is calculated by using the mass average value of the refractive index of two or more types of particle P1. The same applies when the composition of the present invention contains two or more types of particle P2.

[0051] The specific gravity of particle P2 is 2.5 g / cm 3 It is preferable that the density is 2.4 g / cm or less. 3 More preferably, it is 2.2 g / cm or less. 3More preferably, it is 2.0 g / cm or less. 3 The lower limit of the specific gravity of the particles P2 is not particularly limited, but is preferably 0.5 g / cm. 3 It can be more than 0.9g / cm 3 It can be more than that.

[0052] The particles P2 are preferably transparent or white particles. Examples of the particles P2 include inorganic particles and resin particles. Examples of the types of inorganic particles include silica particles, hollow titanium oxide particles, hollow zirconia particles, and the like, and silica particles are preferred. Examples of commercially available inorganic particles include the Sylysia series manufactured by Fuji Silysia Chemical Co., Ltd. (e.g., Sylysia 310P, etc.) and the Sea Hoster series manufactured by Nippon Shokubai Co., Ltd. (e.g., Sea Hoster KE-S250).

[0053] Examples of resin particles include particles made of synthetic resins such as (meth)acrylic resin, styrene resin, polyamide resin, polyimide resin, polyolefin resin, polyurethane resin, polyurea resin, polyester resin, melamine resin, silicone resin, etc., and particles made of natural polymers such as chitin, chitosan, cellulose, crosslinked starch, crosslinked cellulose, etc. Among these, synthetic resin particles are preferably used because they have an advantage that the particle size can be easily controlled.

[0054] As a method for producing resin particles, in the case of a relatively hard resin such as polymethyl methacrylate (PMMA), it is possible to make the resin particles fine by a crushing method, but a method for producing resin particles by an emulsion suspension polymerization method is preferable from the viewpoint of ease and accuracy of controlling the particle size. The method for producing resin particles is described in detail in "Ultrafine particles and materials" edited by the Society of Materials Science of Japan, published by Shokabo in 1993, and "Preparation and application of fine particles and powders" edited by Haruma Kawaguchi, published by CMC Publishing in 2005.

[0055] The resin particles are also available as commercially available products, and examples of such products include MX-40T, MX-80H3wT, MX-150, MX-180TA, MX-300, MX-500, MX-1000, MX-1500H, MR-2HG, MR-7HG, MR-10HG, MR-3GSN, MR-5GSN, MR-7G, MR-10G, MR-5C, and MR-7GC (all manufactured by Soken Chemical & Engineering Co., Ltd., acrylic resin particles), SX-130H, SX-350H, and SX-500H (all manufactured by Soken Chemical & Engineering Co., Ltd., styrene resin particles), MBX-5, MBX-8, MBX-12MBX-15, MBX-20, MB20X-5, and MB30X- No. 5, MB30X-8, MB30X-20, SBX-6, SBX-8, SBX-12, SBX-17 (all manufactured by Sekisui Chemical Co., Ltd., acrylic resin particles), Chemipearl W100, W200, W300, W308, W310, W400, W401, W405, W410, W500, WF640, W700, W800, W900, W950, WP100 (all manufactured by Mitsui Chemicals, Inc., polyolefin resin particles), Tospearl 120 (manufactured by Momentive Performance Technologies, silicone resin particles), Optobeads 2000M (manufactured by Nissan Chemical Co., Ltd., melamine resin particles), and the like.

[0056] It is also preferable that the particle P2 is a hollow particle. A hollow particle refers to a particle having a void portion in which no material constituting the particle exists from the particle surface to the inside. The size, shape, and number of the void portion are not particularly limited. The particle may have an outer shell structure having a void portion in the center, or may have a structure in which a plurality of fine void portions are dispersed inside the particle.

[0057] The porosity of the hollow particles is preferably 1 to 90%. The lower limit of the porosity is preferably 5% or more, more preferably 10% or more. The upper limit of the porosity is preferably 85% or less, more preferably 80% or less. The porosity of the hollow particles refers to the ratio of the volume occupied by voids to the total volume of the hollow particles. The porosity of the hollow particles can be measured by observing the hollow particles using a transmission electron microscope, measuring the outer diameter and void diameter, and calculating the "ratio of the volume occupied by voids to the total volume" using the following formula. Formula: {(pore diameter) 3 / (Outer diameter) 3}×100%

[0058] More specifically, one method is to randomly select 100 hollow particles observed by a transmission electron microscope, measure the circle equivalent diameter of the outside and the void of each of these hollow particles to obtain the outside diameter and void diameter, calculate the porosity using the above formula, and take the average value as the porosity. In addition, if the material of the shell of the particle (its refractive index) and that it is hollow are known, it can also be found from the measurement of the particle refractive index.

[0059] The hollow particles are preferably spherical in shape, but may be of any shape other than spherical, such as irregular shapes.

[0060] The hollow particles may be hollow particles made of an inorganic material (hereinafter also referred to as hollow inorganic particles), or may be hollow particles made of a resin material (hereinafter also referred to as hollow resin particles).

[0061] Materials constituting hollow resin particles include (meth)acrylic resin, styrene resin, polyamide resin, polyimide resin, polyolefin resin, polyurethane resin, polyurea resin, polyester resin, silicone resin, melamine resin, etc., (meth)acrylic resin and styrene resin are preferred, and (meth)acrylic resin is more preferred. Methods for producing hollow resin particles include, for example, a method in which a foaming agent is contained in resin particles and the foaming agent is foamed later, a method in which a volatile substance is enclosed in resin particles and the volatile substance is gasified and expanded later, a method in which a resin particle is melted and a gas such as air is injected therein, a method in which a polymerizable monomer and a non-polymerizable solvent are mixed and polymerized, resin particles containing the solvent are obtained, and then the solvent is removed (hereinafter also referred to as a solvent removal method), etc.

[0062] The hollow inorganic particles are preferably hollow silica particles. That is, the hollow inorganic particles are preferably silica particles having a void in the center. Specific examples of hollow silica particles include hollow particles described in JP2013-237593A and WO2007 / 060884A.

[0063] The content of the particles P2 is preferably 1 to 90% by mass based on the total solid content of the composition. The upper limit is preferably 80% by mass or less, more preferably 70% by mass or less, and even more preferably 60% by mass or less. The lower limit is preferably 2% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more. The composition of the present invention may contain only one type of particles P2, or may contain two or more types. When only one type of particles P2 is contained, better storage stability is likely to be obtained. When two or more types of particles P2 are contained, the angle dependency of light scattering can be further reduced. When two or more types of particles P2 are contained, the total amount thereof is preferably within the above range.

[0064] The total content of the particles P1 and the particles P2 in the total solid content of the composition is preferably 30% by mass or more, more preferably 35% by mass or more, and even more preferably 40% by mass or more, and the upper limit is preferably 90% by mass or less, more preferably 80% by mass or less, and even more preferably 70% by mass or less.

[0065] The ratio of particles P1 to particles P2 in the composition is preferably 20 to 500 parts by mass of particles P1 per 100 parts by mass of particles P2. The upper limit is preferably 450 parts by mass or less, more preferably 400 parts by mass or less, and even more preferably 300 parts by mass or less. The lower limit is preferably 25 parts by mass or more, more preferably 30 parts by mass or more, and even more preferably 35 parts by mass or more.

[0066] <<Film-forming components>> The composition of the present invention contains a film-forming component containing at least one selected from a resin and a polymerizable monomer. The film-forming component used in the present invention contains two or more resins, or contains one or more resins and one or more polymerizable monomers.

[0067] (resin) Resins are blended, for example, to disperse particles in a composition or as a binder. Resins used mainly to disperse particles are also called dispersants. However, these uses of resins are only examples, and resins can also be used for purposes other than these uses.

[0068] The resin may be any known resin, such as (meth)acrylic resin, (meth)acrylamide resin, epoxy resin, ene-thiol resin, polycarbonate resin, polyether resin, polyarylate resin, polysulfone resin, polyethersulfone resin, polyphenylene resin, polyarylene ether phosphine oxide resin, polyimide resin, polyamide resin, polyolefin resin, cyclic olefin resin, polyester resin, styrene resin, silicone resin, and urethane resin.

[0069] The weight average molecular weight (Mw) of the resin is preferably 2000 to 2000000. The upper limit is preferably 1000000 or less, and more preferably 500000 or less. The lower limit is preferably 3000 or more, more preferably 4000 or more, and even more preferably 5000 or more.

[0070] As the resin, a resin having an acid group can be used. Examples of the resin having an acid group include a resin having a repeating unit having an acid group. Examples of the acid group include a carboxyl group, a phosphoric acid group, a sulfo group, and a phenolic hydroxyl group, and the carboxyl group is preferable. The carboxyl group is preferably an aromatic carboxyl group. Here, the aromatic carboxyl group is a group having a structure in which one or more carboxyl groups are bonded to an aromatic ring. In the aromatic carboxyl group, the number of carboxyl groups bonded to the aromatic ring is preferably 1 to 4, and more preferably 1 to 2. Examples of the repeating unit having an aromatic carboxyl group include a repeating unit having the structure shown below. [ka]

[0071] In addition, in the repeating unit having a carboxyl group, the number of atoms constituting the chain connecting the resin main chain and the carboxyl group is preferably 4 or more, more preferably 8 or more. The upper limit of the number of atoms constituting the chain connecting the resin main chain and the carboxyl group is not particularly limited, but is preferably 40 or less, more preferably 30 or less, and even more preferably 20 or less. Examples of repeating units in which the number of atoms constituting the chain connecting the resin main chain and the carboxyl group is 4 or more include repeating units of the structure shown below. The numbers shown in the structural formula are the number of atoms constituting the chain connecting the main chain and the carboxyl group. [ka]

[0072] The resin having an acid group can also be used as an alkali-soluble resin or a dispersant. The acid value of the resin having an acid group is preferably 30 to 500 mgKOH / g. The lower limit is more preferably 50 mgKOH / g or more, and even more preferably 70 mgKOH / g or more. The upper limit is more preferably 400 mgKOH / g or less, even more preferably 200 mgKOH / g or less, particularly preferably 150 mgKOH / g or less, and most preferably 120 mgKOH / g or less. For the resin having an acid group, the description in paragraphs 0558 to 0571 of JP2012-208494A (corresponding to paragraphs 0685 to 0700 of US Patent Application Publication No. 2012 / 0235099A) and the description in paragraphs 0076 to 0099 of JP2012-198408A can be referred to, and the contents of these are incorporated herein.

[0073] As the resin, a resin containing a repeating unit derived from a compound represented by the following formula (ED1) and / or a compound represented by the following formula (ED2) (hereinafter, these compounds may be referred to as "ether dimers") can be used.

[0074] [ka]

[0075] In formula (ED1), R 1 and R 2 each independently represents a hydrogen atom or a hydrocarbon group having 1 to 25 carbon atoms which may have a substituent. [ka] In formula (ED2), R represents a hydrogen atom or an organic group having a carbon number of 1 to 30. Specific examples of formula (ED2) can be found in JP-A-2010-168539.

[0076] For specific examples of ether dimers, reference can be made to paragraph

[0317] of JP2013-029760A, the contents of which are incorporated herein by reference.

[0077] As the resin, a resin containing a repeating unit derived from a compound represented by the following formula (X) can be used. [ka] In formula (X), R 1 represents a hydrogen atom or a methyl group, and R 2 represents an alkylene group having 2 to 10 carbon atoms, R 3 represents a hydrogen atom or an alkyl group having 1 to 20 carbon atoms which may contain a benzene ring. n represents an integer of 1 to 15.

[0078] The resin may be a resin containing a repeating unit having a graft chain. When the resin contains a repeating unit having a graft chain, the steric hindrance caused by the graft chain can more effectively suppress the aggregation of particles in the composition, and excellent storage stability can be obtained. In addition, a phase separation structure can be easily formed in the film during film formation. The resin containing a repeating unit having a graft chain may be used as a dispersant or a binder.

[0079] In the present invention, the graft chain means a polymer chain that branches out from the main chain of a repeating unit. The length of the graft chain is not particularly limited, but as the graft chain becomes longer, the steric repulsion effect becomes stronger, which can improve the dispersibility of particles and facilitate the formation of a phase separation structure. The graft chain preferably has 40 to 10,000 atoms excluding hydrogen atoms, more preferably 50 to 2,000 atoms excluding hydrogen atoms, and even more preferably 60 to 500 atoms excluding hydrogen atoms.

[0080] The graft chain preferably contains at least one repeating unit selected from a repeating unit of a polyester structure, a repeating unit of a polyether structure, a repeating unit of a poly(meth)acrylic structure, a repeating unit of a polyurethane structure, a repeating unit of a polyurea structure, and a repeating unit of a polyamide structure, more preferably contains at least one repeating unit selected from a repeating unit of a polyester structure, a repeating unit of a polyether structure, and a repeating unit of a poly(meth)acrylic structure, and further preferably contains a repeating unit of a polyester structure. Examples of the repeating unit of the polyester structure include repeating units of the structure represented by the following formula (G-1), formula (G-4), or formula (G-5). Examples of the repeating unit of the polyether structure include repeating units of the structure represented by the following formula (G-2). Examples of the repeating unit of the poly(meth)acrylic structure include repeating units of the structure represented by the following formula (G-3). [ka] In the above formula, R G1 and R G2 Each of R represents an alkylene group. G1 and R G2 The alkylene group represented by the formula (I) is not particularly limited, but is preferably a linear or branched alkylene group having 1 to 20 carbon atoms, more preferably a linear or branched alkylene group having 2 to 16 carbon atoms, and even more preferably a linear or branched alkylene group having 3 to 12 carbon atoms. In the above formula, R G3 represents a hydrogen atom or a methyl group. In the above formula, Q G1 represents -O- or -NH-; L G1 represents a single bond or a divalent linking group. Examples of the divalent linking group include an alkylene group (preferably an alkylene group having 1 to 12 carbon atoms), an alkyleneoxy group (preferably an alkyleneoxy group having 1 to 12 carbon atoms), an oxyalkylenecarbonyl group (preferably an oxyalkylenecarbonyl group having 1 to 12 carbon atoms), an arylene group (preferably an arylene group having 6 to 20 carbon atoms), -NH-, -SO-, -SO2 Examples thereof include -, -CO-, -O-, -COO-, OCO-, -S- and combinations of two or more of these. R G4 represents a hydrogen atom or a substituent. Examples of the substituent include an alkyl group, an aryl group, a heteroaryl group, an alkoxy group, an aryloxy group, a heteroaryloxy group, an alkylthioether group, an arylthioether group, and a heteroarylthioether group.

[0081] The terminal structure of the graft chain is not particularly limited. It may be a hydrogen atom or a substituent. Examples of the substituent include an alkyl group, an aryl group, a heteroaryl group, an alkoxy group, an aryloxy group, a heteroaryloxy group, an alkylthioether group, an arylthioether group, and a heteroarylthioether group. Among them, from the viewpoint of improving the dispersibility of particles, a group having a steric repulsion effect is preferable, and an alkyl group or an alkoxy group having 5 to 24 carbon atoms is preferable. The alkyl group and the alkoxy group may be any of a straight chain, a branched group, and a cyclic group, and a straight chain or a branched group is preferable.

[0082] The graft chain preferably has a structure represented by the following formula (G-1a), formula (G-2a), formula (G-3a), formula (G-4a) or formula (G-5a). [ka]

[0083] In the above formula, R G1 and R G2 each represents an alkylene group, and R G3 represents a hydrogen atom or a methyl group, and Q G1 represents -O- or -NH-; L G1 represents a single bond or a divalent linking group, R G4 represents a hydrogen atom or a substituent, W 100 represents a hydrogen atom or a substituent. n1 to n5 each independently represent an integer of 2 or more. R G1 ~R G4 , QG1 , L G1 Regarding R explained in formulas (G-1) to (G-5), G1 ~R G4 , Q G1 , L G1 The same definition and preferred range are also the same.

[0084] In formulas (G-1a) to (G-5a), W 100 is preferably a substituent. Examples of the substituent include an alkyl group, an aryl group, a heteroaryl group, an alkoxy group, an aryloxy group, a heteroaryloxy group, an alkylthioether group, an arylthioether group, and a heteroarylthioether group. Among them, from the viewpoint of improving the dispersibility of pigments and the like, a group having a steric repulsion effect is preferred, and an alkyl group or an alkoxy group having 5 to 24 carbon atoms is preferred. The alkyl group and the alkoxy group may be linear, branched, or cyclic, and linear or branched is preferred.

[0085] In the formulas (G-1a) to (G-5a), n1 to n5 each preferably represents an integer of 2 to 100, more preferably an integer of 2 to 80, and further preferably an integer of 8 to 60.

[0086] In formula (G-1a), when n1 is 2 or more, R in each repeating unit G1 may be the same or different. G1 In the case where the repeating units have two or more different repeating units, the arrangement of the repeating units is not particularly limited and may be random, alternating, or block. The same applies to the formulae (G-2a) to (G-5a). Among them, the graft chain is preferably a structure represented by the formula (G-1a), (G-4a), or (G-5a), in which R G1 In other words, the n1 R G1 , n4 R in formula (G-4a) G1 and n5 R in formula (G-5a) G1It is preferable that the alkylene group contains two or more types of alkylene groups having different numbers of carbon atoms.

[0087] An example of the repeating unit having a graft chain is a repeating unit represented by the following formula (A-1-2). [ka]

[0088] In formula (A-1-2), X 2 represents the main chain of the repeating unit, and L 2 represents a single bond or a divalent linking group, W 1 represents a graft chain.

[0089] X in formula (A-1-2) 2 The main chain of the repeating unit represented by formula (A-1-1) is 1 The preferred ranges are the same as those described above. 2 Examples of the divalent linking group represented by the formula (I) include an alkylene group (preferably an alkylene group having 1 to 12 carbon atoms), an arylene group (preferably an arylene group having 6 to 20 carbon atoms), -NH-, -SO-, -SO 2 Examples of the W in formula (A-1-2) include -, -CO-, -O-, -COO-, OCO-, -S-, and a combination of two or more of these. 1 The graft chain represented by the formula (I) includes the graft chains described above.

[0090] Specific examples of the repeating unit represented by formula (A-1-2) include a repeating unit represented by the following formula (A-1-2a) and a repeating unit represented by the following formula (A-1-2b). [ka]

[0091] In formula (A-1-2a), R b1 ~R b3 each independently represents a hydrogen atom or an alkyl group; Q b1represents -CO-, -COO-, -OCO-, -CONH- or a phenylene group; L 2 represents a single bond or a divalent linking group; W 1 represents a graft chain. R b1 ~R b3 The number of carbon atoms in the alkyl group represented by Q is preferably 1 to 10, more preferably 1 to 3, and even more preferably 1. b1 is preferably -COO- or -CONH-, and more preferably -COO-.

[0092] In formula (A-1-2b), R b10 and R b11 each independently represents a hydrogen atom or an alkyl group; m2 represents an integer of 1 to 5; L 2 represents a single bond or a divalent linking group; W 1 represents a graft chain. R b10 and R b11 The alkyl group represented by the formula (I) preferably has 1 to 10 carbon atoms, and more preferably has 1 to 3 carbon atoms.

[0093] The weight average molecular weight (Mw) of the repeating unit having a graft chain is preferably 1000 or more, more preferably 1000 to 10000, and even more preferably 1000 to 7500. In the present invention, the weight average molecular weight of the repeating unit having a graft chain is a value calculated from the weight average molecular weight of the raw material monomer used in the polymerization of the repeating unit. For example, the repeating unit having a graft chain can be formed by polymerizing a macromonomer. Here, the macromonomer means a polymeric compound having a polymerizable group introduced at the polymer end. When the repeating unit having a graft chain is formed using a macromonomer, the weight average molecular weight of the macromonomer corresponds to the repeating unit having a graft chain.

[0094] It is also preferable that the resin containing a repeating unit having a graft chain further contains a repeating unit derived from a (meth)acrylic acid ester, which can further improve the light scattering properties of the obtained film.

[0095] It is also preferable that the resin containing the repeating unit having a graft chain further has a repeating unit having an acid group and a repeating unit having neither a graft chain nor an acid group. According to this embodiment, the phase separation size in the film can be suppressed from becoming excessively large, and a film having better light scattering properties can be formed. Examples of the acid group in the repeating unit having an acid group include a carboxyl group, a phosphoric acid group, a sulfo group, and a phenolic hydroxyl group, and the carboxyl group is preferable. In addition, the carboxyl group is preferably an aromatic carboxyl group. In addition, in the repeating unit having a carboxyl group, the number of atoms constituting the chain connecting the main chain of the resin and the carboxyl group is preferably 4 or more, and more preferably 8 or more. The upper limit of the number of atoms constituting the chain connecting the main chain of the resin and the carboxyl group is not particularly limited, but is preferably 40 or less, more preferably 30 or less, and even more preferably 20 or less.

[0096] In the composition of the present invention, it is also preferable to use a resin having a structure in which a polymer chain is bonded to a trivalent or higher linking group. Such a resin can be, for example, a resin having a structure represented by the following formula (SP-1) (hereinafter, also referred to as resin (SP-1)). Resin (SP-1) can be preferably used as a dispersant, but may also be used as a binder. [ka] In the formula, Z 1 represents a (m+n)-valent linking group, Y 1 and Y 2 each independently represents a single bond or a linking group, A 1 represents a group containing a substituent selected from a heterocyclic group, an acid group, a group having a basic nitrogen atom, a urea group, a urethane group, a group having a coordinating oxygen atom, a hydrocarbon group having 4 or more carbon atoms, an alkoxysilyl group, an epoxy group, an isocyanate group, and a hydroxy group, P 1 represents the polymer chain, n represents 1 to 20, m represents 1 to 20, and m+n represents 3 to 21; n Y's 1 and A 1 may be the same or different, m Y's 2 and P 1 may be the same or different.

[0097] Z in formula (SP-1) 1 , A 1 and P 1 At least one of the above may contain an ethylenically unsaturated bond-containing group. Examples of the ethylenically unsaturated bond-containing group include a vinyl group, a vinyloxy group, an allyl group, a methallyl group, a (meth)acryloyl group, a styrene group, a cinnamoyl group, and a maleimide group, of which a (meth)acryloyl group, a styrene group, and a maleimide group are preferred, a (meth)acryloyl group is more preferred, and an acryloyl group is particularly preferred.

[0098] When the resin (SP-1) contains an ethylenically unsaturated bond-containing group, such a resin corresponds to a polymerizable resin described later. The ethylenically unsaturated bond-containing group is represented by Z in the formula (SP-1). 1 , A 1 and P 1 However, it is acceptable if it is included in any of the above. 1 It is preferable that the compound is included in P. 1 When P contains an ethylenically unsaturated bond-containing group, 1 is preferably a polymer chain having a repeating unit containing an ethylenically unsaturated bond-containing group in the side chain.

[0099] In formula (SP-1), A 1 represents a group containing the above-mentioned substituent. As the substituent, a heterocyclic group, an acid group, a group having a basic nitrogen atom, a hydrocarbon group having 4 or more carbon atoms, and a hydroxyl group are preferable, and an acid group is more preferable. As the acid group, a carboxyl group, a sulfo group, and a phosphate group can be mentioned, and a carboxyl group is preferable. In addition, the carboxyl group is preferably an aromatic carboxyl group.

[0100] The above-mentioned substituents are each one A 1 It is sufficient that at least one is contained in the compound, but two or more may be contained. 1 Preferably, A contains 1 to 10 of the above-mentioned substituents, and more preferably contains 1 to 6 of them. 1 The group containing the above-mentioned substituent represented by can be a group formed by bonding the above-mentioned substituent to a linking group consisting of 1 to 200 carbon atoms, 0 to 20 nitrogen atoms, 0 to 100 oxygen atoms, 1 to 400 hydrogen atoms, and 0 to 40 sulfur atoms. For example, can be a group formed by bonding one or more acid groups via a chain saturated hydrocarbon group having 1 to 10 carbon atoms, a cyclic saturated hydrocarbon group having 3 to 10 carbon atoms, or an aromatic hydrocarbon group having 5 to 10 carbon atoms. The above chain saturated hydrocarbon group, cyclic saturated hydrocarbon group, and aromatic hydrocarbon group can further have a substituent. Examples of the substituent can include an alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 16 carbon atoms, a hydroxyl group, a carboxyl group, an amino group, a sulfonamide group, an N-sulfonylamido group, an acyloxy group having 1 to 6 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, a halogen atom, an alkoxycarbonyl group having 2 to 7 carbon atoms, a cyano group, a carbonate ester group, and an ethylenically unsaturated bond-containing group. In addition, the above substituent itself is A 1 may be also possible.

[0101] A 1 The chemical formula weight is preferably 30 to 2000. The upper limit is preferably 1000 or less, and more preferably 800 or less. The lower limit is preferably 50 or more, and more preferably 100 or more.

[0102] In formula (SP-1), Z 1 represents a (m+n)-valent linking group. Examples of the (m+n)-valent linking group include groups consisting of 1 to 100 carbon atoms, 0 to 10 nitrogen atoms, 0 to 50 oxygen atoms, 1 to 200 hydrogen atoms, and 0 to 20 sulfur atoms. Examples of the (m+n)-valent linking group include the following structural units or groups consisting of two or more of the following structural units combined together (which may form a ring structure).

[0103] [ka]

[0104] The (m+n)-valent linking group may have a substituent, such as an alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 16 carbon atoms, a hydroxyl group, an amino group, a carboxyl group, a sulfonamido group, an N-sulfonylamido group, an acyloxy group having 1 to 6 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, a halogen atom, an alkoxycarbonyl group having 2 to 7 carbon atoms, a cyano group, a carbonate ester group, or an ethylenically unsaturated bond-containing group.

[0105] Z 1 The (m+n)-valent linking group represented by is preferably a group represented by any one of the following formulae: [ka] L 3 represents a trivalent group. 3 represents a single bond or a divalent linking group, and there are three T 3 may be the same or different from each other. L 4 represents a tetravalent group. 4 represents a single bond or a divalent linking group, and there are four T 4 may be the same or different from each other. L 5 represents a pentavalent group. 5 represents a single bond or a divalent linking group, and there are five T 5 may be the same or different from each other. L 6 represents a hexavalent group. 6 represents a single bond or a divalent linking group, and there are six T 6 may be the same or different from each other.

[0106] T 3 ~T 6 The divalent linking group represented by is -CH 2Examples of the linking group include -, -O-, -CO-, -COO-, -OCO-, -NH-, an aliphatic ring group, an aromatic hydrocarbon ring group, a heterocyclic group, and a group consisting of a combination thereof. The aliphatic ring group, the aromatic hydrocarbon ring group, and the heterocyclic group may be a monocyclic group or a condensed ring. The divalent linking group may further have the above-mentioned substituent.

[0107] L 3 Examples of the trivalent group represented by L include the above divalent linking groups in which one hydrogen atom has been removed. 4 Examples of the tetravalent group represented by L include groups in which two hydrogen atoms have been removed from the divalent linking groups described above. 5 Examples of the pentavalent group represented by L include groups in which three hydrogen atoms have been removed from the divalent linking groups described above. 6 Examples of the hexavalent group represented by include groups in which four hydrogen atoms have been removed from the divalent linking groups described above. 3 ~L 6 The trivalent to hexavalent group represented by may further have the above-mentioned substituent.

[0108] Z 1 The chemical formula weight of Z is preferably 20 to 3000. The upper limit is preferably 2000 or less, more preferably 1500 or less. The lower limit is preferably 50 or more, more preferably 100 or more. 1 If the chemical formula weight of Z is within the above range, the dispersibility of the pigment in the composition can be improved. 1 The formula weight is a value calculated from the structural formula.

[0109] For specific examples of the (m+n)-valent linking group, reference can be made to paragraphs 0043 to 0055 of JP2014-177613A, the contents of which are incorporated herein by reference.

[0110] In formula (SP-1), Y 1 and Y 2Each of Y independently represents a single bond or a linking group. Examples of the linking group include groups consisting of 1 to 100 carbon atoms, 0 to 10 nitrogen atoms, 0 to 50 oxygen atoms, 1 to 200 hydrogen atoms, and 0 to 20 sulfur atoms. The above groups may further have the above-mentioned substituents. 1 and Y 2 Examples of the linking group represented by the formula (I) include the following structural units or groups formed by combining two or more of the following structural units.

[0111] [ka]

[0112] In formula (SP-1), P 1 represents a polymer chain. P 1 The polymer chain represented by is preferably a polymer chain having, in the main chain, at least one repeating unit selected from a repeating unit of a poly(meth)acrylic structure, a repeating unit of a polyether structure, a repeating unit of a polyester structure, a repeating unit of a polyamide structure, a repeating unit of a polyimide structure, a repeating unit of a polyimine structure, and a repeating unit of a polyurethane structure. 1 The polymer chain represented by formula (P1-1) is preferably a polymer chain containing repeating units represented by the following formulas (P1-1) to (P1-5). [ka]

[0113] In the above formula, R G1 and R G2 Each of R represents an alkylene group. G1 and R G2The alkylene group represented by the formula (I) is preferably a linear or branched alkylene group having 1 to 20 carbon atoms, more preferably a linear or branched alkylene group having 2 to 16 carbon atoms, and even more preferably a linear or branched alkylene group having 3 to 12 carbon atoms. The alkylene group may have a substituent. Examples of the substituent include an aryl group, a heteroaryl group, an alkoxy group, an aryloxy group, a heteroaryloxy group, an alkylthioether group, an arylthioether group, a heteroarylthioether group, and an ethylenically unsaturated bond-containing group. In the above formula, R G3 represents a hydrogen atom or a methyl group. In the above formula, Q G1 represents -O- or -NH-; L G1 represents a single bond or an arylene group; L G2 represents a single bond or a divalent linking group. G1 is preferably -O-. G1 is preferably a single bond. G2 Examples of the divalent linking group represented by the formula (I) include an alkylene group (preferably an alkylene group having 1 to 12 carbon atoms), an arylene group (preferably an arylene group having 6 to 20 carbon atoms), -NH-, -SO-, -SO 2 Examples thereof include -, -CO-, -O-, -COO-, -OCO-, -S-, -NHCO-, -CONH-, and groups formed by combining two or more of these. R G4 represents a hydrogen atom or a substituent. Examples of the substituent include an alkyl group, an aryl group, a heteroaryl group, an alkoxy group, an aryloxy group, a heteroaryloxy group, an alkylthioether group, an arylthioether group, a heteroarylthioether group, an ethylenically unsaturated bond-containing group, and an acid group.

[0114] P 1 The number of repetitions of the repeating unit in is preferably 3 to 2000. The upper limit is preferably 1500 or less, more preferably 1000 or less. The lower limit is preferably 5 or more, more preferably 7 or more. 1is preferably a polymer chain having a repeating unit containing an ethylenically unsaturated bond-containing group in a side chain. 1 The proportion of repeating units containing an ethylenically unsaturated bond-containing group in a side chain in all repeating units constituting P is preferably 1 mol % or more, more preferably 2 mol % or more, and even more preferably 3 mol % or more. The upper limit can be set to 100 mol %. 1 is a polymer chain having a repeating unit containing an ethylenically unsaturated bond-containing group in a side chain, 1 It is also preferable that P contains other repeating units in addition to the repeating unit containing an ethylenically unsaturated bond-containing group in the side chain. Examples of the other repeating units include a repeating unit containing an acid group in the side chain. 1 By including a repeating unit containing an acid group in the side chain in addition to the repeating unit containing an ethylenically unsaturated bond-containing group in the side chain, the generation of development residues can be more effectively suppressed when a pattern is formed by photolithography. 1 If contains a repeating unit containing an acid group in the side chain, P 1 The proportion of repeating units having an acid group in the side chain among all repeating units constituting the polymer is preferably 50 mol % or less, more preferably 2 to 48 mol %, and even more preferably 4 to 46 mol %.

[0115] P 1 The weight average molecular weight of the polymer chain represented by is preferably 1000 or more, more preferably 1000 to 10000. The upper limit is preferably 9000 or less, more preferably 6000 or less, and even more preferably 3000 or less. The lower limit is preferably 1200 or more, and more preferably 1400 or more. 1 The weight average molecular weight is a value calculated from the weight average molecular weight of the raw material used for introducing the polymer chain.

[0116] Specific examples of resin (SP-1) include polymer compounds C-1 to C-31 described in paragraphs 0196 to 0209 of JP 2013-043962 A, polymer compounds (C-1) to (C-61) described in paragraphs 0256 to 0269 of JP 2014-177613 A, and resins having a structure described in paragraph 0061 of WO 2018 / 163668 A, the contents of which are incorporated herein by reference.

[0117] In the composition of the present invention, a resin having a polymerizable group (hereinafter, also referred to as a polymerizable resin) can be used as the resin. Examples of the polymerizable group include an ethylenically unsaturated bond-containing group, an epoxy group, and a cyclic ether group such as an oxetane group. By using a polymerizable resin, excessive phase separation can be suppressed in the film after curing. The amount of polymerizable groups contained in the polymerizable resin is preferably 0.01 to 5.0 mmol / g. The upper limit is more preferably 4.0 mmol / g or less, further preferably 3.0 mmol / g or less, even more preferably 2.0 mmol / g or less, and particularly preferably 1.5 mmol / g or less. The lower limit is preferably 0.1 mmol / g or more, and more preferably 0.2 mmol / g or more. The amount of polymerizable groups in the polymerizable resin is a numerical value representing the molar amount of polymerizable groups per 1 g of solid content of the polymerizable resin. For the polymerizable group value of the polymerizable resin, if it can be calculated from the raw materials used in the synthesis of the polymerizable resin, the value calculated from the raw materials used in the synthesis is used. In addition, for the polymerizable group value of the polymerizable resin, if it cannot be calculated from the raw materials used in the synthesis of the polymerizable resin, for example, in the case of an ethylenically unsaturated group, a value measured using a hydrolysis method is used. Specifically, the low molecular weight component (a) at the polymerizable group site is extracted from the polymerizable resin by alkali treatment, and its content is measured by high performance liquid chromatography (HPLC), and calculated from the following formula. In addition, in the case where the polymerizable group cannot be extracted from the polymerizable resin by alkali treatment, a value measured by NMR (nuclear magnetic resonance) is used. Polymerizable group value of polymerizable resin [mmol / g] = (content of low molecular weight component (a) [ppm] / molecular weight of low molecular weight component (a) [g / mol]) / (weight value of polymerizable resin [g] × (solid content concentration of polymerizable resin [mass%] / 100) × 10)

[0118] The polymerizable resin may be a resin containing a repeating unit having a polymerizable group in a side chain, a resin represented by the above formula (SP-1), 1 , A 1 and P 1 At least one of the above may contain a polymerizable group.

[0119] An example of a repeating unit having a polymerizable group in a side chain is a repeating unit represented by the following formula (A-1-1). A resin containing a repeating unit represented by the following formula (A-1-1) may be used as a dispersant or a binder. In the polymerizable resin, the content of the repeating unit having a polymerizable group is preferably 10 mol % or more, more preferably 10 to 80 mol %, and even more preferably 20 to 70 mol %, of all repeating units in the polymerizable resin. [ka]

[0120] In formula (A-1-1), X 1 represents the main chain of the repeating unit, and L 1 represents a single bond or a divalent linking group; Y 1 represents a polymerizable group.

[0121] In formula (A-1-1), X 1The main chain of the repeating unit represented by is not particularly limited. There is no particular limitation as long as it is a linking group formed from a known polymerizable monomer. For example, poly(meth)acrylic linking groups, polyalkyleneimine linking groups, polyester linking groups, polyurethane linking groups, polyurea linking groups, polyamide linking groups, polyether linking groups, polystyrene linking groups, etc. can be mentioned. From the viewpoint of availability of raw materials and suitability for production, poly(meth)acrylic linking groups and polyalkyleneimine linking groups are preferred, and poly(meth)acrylic linking groups are more preferred.

[0122] In formula (A-1-1), L 1 Examples of the divalent linking group represented by the formula (I) include an alkylene group (preferably an alkylene group having 1 to 12 carbon atoms), an alkyleneoxy group (preferably an alkyleneoxy group having 1 to 12 carbon atoms), an oxyalkylenecarbonyl group (preferably an oxyalkylenecarbonyl group having 1 to 12 carbon atoms), an arylene group (preferably an arylene group having 6 to 20 carbon atoms), -NH-, -SO-, -SO 2 Examples of the alkylene group include -, -CO-, -O-, -COO-, -OCO-, -S-, and a group formed by combining two or more of these. The alkylene group, the alkylene group in the alkyleneoxy group, and the alkylene group in the oxyalkylenecarbonyl group may be linear, branched, or cyclic, and linear or branched is preferred. The alkylene group, the alkylene group in the alkyleneoxy group, and the alkylene group in the oxyalkylenecarbonyl group may have a substituent or may be unsubstituted. Examples of the substituent include a hydroxy group and an alkoxy group, and a hydroxy group is preferred from the viewpoint of production suitability.

[0123] In formula (A-1-1), Y 1The polymerizable group represented by includes an ethylenically unsaturated bond-containing group and a cyclic ether group, and is preferably an ethylenically unsaturated bond-containing group.The ethylenically unsaturated bond-containing group includes a vinyl group, a vinyloxy group, an allyl group, a methallyl group, a (meth)acryloyl group, a styrene group, a cinnamoyl group, and a maleimide group, and is preferably a (meth)acryloyl group, a styrene group, or a maleimide group, more preferably a (meth)acryloyl group, and particularly preferably an acryloyl group.

[0124] The resin containing the repeating unit represented by the formula (A-1-1) may further contain a repeating unit having a graft chain. Examples of the repeating unit having a graft chain include the repeating unit represented by the formula (A-1-2) described above. In the polymerizable resin, the content of the repeating unit having a graft chain is preferably 1.0 to 60 mol %, more preferably 1.5 to 50 mol %, of the total repeating units of the polymerizable resin.

[0125] The resin containing the repeating unit represented by the formula (A-1-1) may further contain a repeating unit having an acid group. The content of the repeating unit having an acid group is preferably 80 mol % or less, more preferably 10 to 80 mol %, of all the repeating units in the polymerizable resin.

[0126] The film-forming component preferably contains a resin as a dispersant for particles and a resin as a binder. In addition, the resin as a binder is preferably one that has low compatibility with the resin as a dispersant for particles. By using such resins in combination, the phase separation structure of the first phase and the second phase described above is easily formed in the film obtained by using the composition, and the light scattering property of the obtained film is easily improved.

[0127] The resin as the dispersant and the resin as the binder can be appropriately selected from the above-mentioned resins. The resin used as the dispersant is preferably a resin having an acid group. The dispersant is also available as a commercially available product, and specific examples thereof include the Disperbyk series manufactured by BYK-Chemie (e.g., Disperbyk-111, 2001, etc.), the Solsperse series manufactured by Lubrizol Japan Co., Ltd. (e.g., Solsperse 20000, 76500, etc.), and the Ajisper series manufactured by Ajinomoto Fine-Techno Co., Ltd. In addition, the product described in paragraph number 0129 of JP 2012-137564 A and the product described in paragraph number 0235 of JP 2017-194662 A can also be used as a dispersant.

[0128] In addition, the film-forming component preferably contains two or more resins selected from a resin A1 having a structure in which a polymer chain is bonded to a trivalent or higher linking group and a resin A2 having a repeating unit with a graft chain. In this case, it is preferable that at least one of the two or more resins is a resin serving as a dispersant, and the remaining is a resin serving as a binder. That is, the resin serving as a dispersant and the resin serving as a binder preferably use a resin A1 having a structure in which a polymer chain is bonded to a trivalent or higher linking group and a resin A2 having a repeating unit with a graft chain.

[0129] Preferred embodiments of the resin contained in the film-forming component include the following embodiments. (1) An embodiment including a resin A1-1 having a structure in which a polymer chain is bonded to a trivalent or higher linking group, and a resin A1-2 having a structure in which a polymer chain containing a repeating unit having a structure different from that of the polymer chain of the resin A1-1 is bonded to a trivalent or higher linking group. (2) An embodiment including a resin A2-1 having a repeating unit with a graft chain, and a resin A2-2 having a repeating unit with a graft chain that includes a repeating unit with a structure different from that of the graft chain of the resin A2-1. (3) An embodiment including a resin A1-3 having a structure in which a polymer chain is bonded to a trivalent or higher linking group, and a resin A2-3 having a repeating unit having a graft chain that includes a repeating unit having a structure different from that of the polymer chain of the resin A1-3.

[0130] The repeating units having different structures refer to repeating units having different types of main chains. Therefore, even if the types of substituents bonded to the main chains are different, repeating units having the same type of main chain (for example, repeating units having poly(meth)acrylic structures, repeating units having polyester structures, etc.) are considered to be repeating units having the same structure.

[0131] In addition, the main chain structure of the polymer chain contained in the resin A1 or the graft chain contained in the resin A2 used as a dispersant and the structure of the repeating unit of the polymer chain contained in the resin A1 or the graft chain contained in the resin A2 used as a binder are preferably different from each other. Since resins having polymer chains or graft chains containing repeating units of different structures tend to have low compatibility, when such a combination of dispersant and binder is contained, it is easy to form the phase separation structure of the above-mentioned first phase and second phase, and it is easy to further improve the light scattering property of the obtained film.

[0132] Examples of resin combinations with low compatibility include the following: A combination of a resin A1 having a polymer chain containing a repeating unit of a poly(meth)acrylic structure or a resin A2 having a graft chain containing a repeating unit of a poly(meth)acrylic structure, and a resin A1 having a polymer chain containing a repeating unit of a polyester structure or a resin A2 having a graft chain containing a repeating unit of a polyester structure. -Combination of polyamide resin and phenolic resin.

[0133] It is also preferable that the film-forming component contains at least one selected from a resin having a structure in which a polymer chain containing a repeating unit of a polyester structure is bonded to a trivalent or higher linking group and a resin containing a repeating unit having a graft chain containing a repeating unit of a polyester structure. By containing such a resin in the film-forming component, the effect of improving the phase separation efficiency can be expected.

[0134] The resin content is preferably 0.1 to 60% by mass based on the total solid content of the composition. The lower limit is preferably 1% by mass or more, more preferably 5% by mass or more. The upper limit is preferably 50% by mass or less, more preferably 45% by mass or less.

[0135] Furthermore, the resin used in the composition preferably contains 10% by mass or more of a polymerizable resin (preferably a resin containing an ethylenically unsaturated bond-containing group), more preferably 20% by mass or more, and even more preferably 30% by mass or more.

[0136] Furthermore, the resin used in the composition preferably contains 10% by mass or more of the resin as a dispersant, more preferably 20% by mass or more, and even more preferably 30% by mass or more.

[0137] Furthermore, the resin used in the composition preferably contains 40 to 250 parts by mass of the resin as a binder per 100 parts by mass of the resin as a dispersant, more preferably contains 50 to 225 parts by mass, and even more preferably contains 60 to 200 parts by mass of the resin as a binder.

[0138] The content of the dispersant in the composition is preferably 5 to 150 parts by mass relative to 100 parts by mass of the above-mentioned particles. The upper limit is preferably 140 parts by mass or less, more preferably 125 parts by mass or less, and even more preferably 100 parts by mass or less. The lower limit is preferably 10 parts by mass or more, more preferably 15 parts by mass or more, and even more preferably 25 parts by mass or more.

[0139] It is also preferable that the composition of the present invention contains a resin having a polymerizable group and a resin having no polymerizable group. According to this embodiment, phase separation is more likely to proceed due to polymerizable phase separation. In this case, the content of the resin having a polymerizable group is preferably 5 to 90 parts by mass relative to 100 parts by mass of the resin having no polymerizable group. The upper limit is preferably 85 parts by mass or less, more preferably 80 parts by mass or less, and even more preferably 70 parts by mass or less. The lower limit is preferably 10 parts by mass or more, more preferably 15 parts by mass or more, and even more preferably 25 parts by mass or more.

[0140] The composition of the present invention also preferably contains a resin having a structure in which a polymer chain is bonded to a trivalent or higher linking group and a resin containing a repeating unit having a graft chain. In this case, it is preferable that one of the resins having a structure in which a polymer chain is bonded to a trivalent or higher linking group and the resin containing a repeating unit having a graft chain is a dispersant and the other resin is a binder. The content of the resin having a structure in which a polymer chain is bonded to a trivalent or higher linking group is preferably 40 to 250 parts by mass relative to 100 parts by mass of the resin containing a repeating unit having a graft chain. The upper limit is preferably 250 parts by mass or less, more preferably 225 parts by mass or less, and even more preferably 200 parts by mass or less. The lower limit is preferably 40 parts by mass or more, more preferably 50 parts by mass or more, and even more preferably 60 parts by mass or more. The total content of the resin having a structure in which a polymer chain is bonded to a trivalent or higher linking group and the resin containing a repeating unit having a graft chain in the resin contained in the composition is preferably 20% by mass or more, and more preferably 30% by mass or more.

[0141] (Polymerizable monomer) As the polymerizable monomer, a known compound capable of being crosslinked by radicals, acid or heat can be used. For example, a compound having an ethylenically unsaturated bond-containing group, a compound having a cyclic ether group, etc. can be mentioned. As the ethylenically unsaturated bond-containing group, a vinyl group, a (meth)allyl group, a (meth)acryloyl group, etc. can be mentioned. As the cyclic ether group, an epoxy group, an oxetanyl group, etc. can be mentioned. As the polymerizable monomer, a radical polymerizable monomer or a cation polymerizable monomer is preferable, and a radical polymerizable monomer is more preferable.

[0142] The polymerizable monomer used in the present invention may be a polymerizable monomer containing a ring structure, and in this case, it is more preferable that the polymerizable monomer is a radical polymerizable monomer containing a ring structure. When a polymerizable monomer containing a ring structure is used, phase separation from the resin tends to occur. In particular, when a radical polymerizable monomer containing a ring structure is used, the above effect is remarkable. The ring structure contained in the polymerizable monomer is preferably an aliphatic ring because the above effect is more likely to be obtained. In addition, the aliphatic ring is preferably an aliphatic crosslinked ring. The aliphatic crosslinked ring is an aliphatic ring having a structure in which two or more atoms that are not adjacent to each other are connected in one aliphatic ring. Specific examples of the aliphatic crosslinked ring include a tricyclodecane ring and an adamantane ring, and the tricyclodecane ring is preferable. The number of ring structures contained in the polymerizable monomer is preferably 1 to 5 from the viewpoint of the mobility of the monomer, more preferably 1 to 3, and more preferably 1. Specific examples of the radical polymerizable monomer containing a ring structure include dimethylol-tricyclodecane diacrylate and 1,3-adamantanediol diacrylate.

[0143] The radical polymerizable monomer is not particularly limited as long as it is a compound that can be polymerized by the action of a radical. The radical polymerizable monomer is preferably a compound having an ethylenically unsaturated bond-containing group, more preferably a compound having two or more ethylenically unsaturated bond-containing groups, and even more preferably a compound having three or more ethylenically unsaturated bond-containing groups. The upper limit of the number of ethylenically unsaturated bond-containing groups is, for example, preferably 15 or less, more preferably 6 or less. Examples of the ethylenically unsaturated bond-containing group include a vinyl group, a styryl group, a (meth)allyl group, and a (meth)acryloyl group, and the like, and the (meth)acryloyl group is preferred. The radical polymerizable monomer is preferably a 3-15 functional (meth)acrylate compound, and more preferably a 3-6 functional (meth)acrylate compound. In addition, the radical polymerizable monomer is also preferably one that contains a ring structure.

[0144] The molecular weight of the radical polymerizable monomer is preferably 200 to 3000. The upper limit of the molecular weight is preferably 2500 or less, more preferably 2000 or less. The lower limit of the molecular weight is preferably 250 or more, more preferably 300 or more.

[0145] The radical polymerizable monomer is also preferably a compound having at least one addition-polymerizable ethylene group and an ethylenically unsaturated bond-containing group having a boiling point of 100° C. or higher under normal pressure. Examples thereof include monofunctional acrylates and methacrylates such as polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, and phenoxyethyl(meth)acrylate; polyethylene glycol di(meth)acrylate, trimethylolethane tri(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, hexanediol(meth)acrylate, trimethylolpropane tri(acryloyloxypropyl)ether, tri(acryloyloxyethyl)isocyanurate, and mixtures thereof, with pentaerythritol tetra(meth)acrylate being preferred.

[0146] As the radical polymerizable monomer, the compounds represented by formulae (MO-1) to (MO-5) can also be suitably used. In the formulae, when T is an oxyalkylene group, the end of T on the carbon atom side is bonded to R.

[0147] [ka]

[0148] In the above formula, n is 0 to 14, and m is 1 to 8. R and T present in a single molecule may be the same or different. In each of the compounds represented by formulae (MO-1) to (MO-5), at least one of the R present is -OC(=O)CH=CH 2 , or -OC(=O)C(CH 3 )=CH 2Specific examples of the compounds represented by formulae (MO-1) to (MO-5) include the compounds described in paragraphs 0248 to 0251 of JP-A No. 2007-269779, the contents of which are incorporated herein by reference.

[0149] Examples of radical polymerizable monomers include dipentaerythritol triacrylate (commercially available product: KAYARAD D-330; manufactured by Nippon Kayaku Co., Ltd.), dipentaerythritol tetraacrylate (commercially available product: KAYARAD D-320; manufactured by Nippon Kayaku Co., Ltd.), dipentaerythritol penta(meth)acrylate (commercially available product: KAYARAD D-310; manufactured by Nippon Kayaku Co., Ltd.), and dipentaerythritol hexa(meth)acrylate (commercially available product: KAYARAD DPHA (manufactured by Nippon Kayaku Co., Ltd.), NK Ester A-DPH-12E (manufactured by Shin-Nakamura Chemical Co., Ltd.), and compounds in which the (meth)acryloyl group is bonded via an ethylene glycol and / or propylene glycol residue (e.g., SR454 and SR499, available from Sartomer Co., Ltd.), diglycerin EO (ethylene oxide) modified (meth)acrylate (commercially available product is M-460, manufactured by Toagosei Co., Ltd.), pentaerythritol tetraacrylate (NK Ester A-TMMT, manufactured by Shin-Nakamura Chemical Co., Ltd.), 1,6-hexanediol diacrylate (KAYARAD HDDA, manufactured by Nippon Kayaku Co., Ltd.), KAYARAD RP-1040 (manufactured by Nippon Kayaku Co., Ltd.), Aronix TO-2349 (manufactured by Toagosei Co., Ltd.), NK Oligo UA-7200 (manufactured by Shin-Nakamura Chemical Co., Ltd.), 8UH-1006, 8UH-1012 (manufactured by Taisei Fine Chemical Co., Ltd.), Light Acrylate POB-A0 (manufactured by Kyoeisha Chemical Co., Ltd.), etc. can also be used.

[0150] In addition, it is also preferable to use, as the radical polymerizable monomer, a trifunctional (meth)acrylate compound such as trimethylolpropane tri(meth)acrylate, trimethylolpropane propyleneoxy-modified tri(meth)acrylate, trimethylolpropane ethyleneoxy-modified tri(meth)acrylate, isocyanuric acid ethyleneoxy-modified tri(meth)acrylate, or pentaerythritol tri(meth)acrylate. Commercially available trifunctional (meth)acrylate compounds include ARONIX M-309, M-310, M-321, M-350, M-360, M-313, M-315, M-306, M-305, M-303, M-452, and M-450 (manufactured by Toagosei Co., Ltd.), NK Ester A9300, A-GLY-9E, A-GLY-20E, A-TMM-3, A-TMM-3L, A-TMM-3LM-N, A-TMPT, and TMPT (manufactured by Shin-Nakamura Chemical Co., Ltd.), KAYARAD GPO-303, TMPTA, THE-330, TPA-330, and PET-30 (manufactured by Nippon Kayaku Co., Ltd.).

[0151] The radical polymerizable monomer may have an acid group such as a carboxyl group, a sulfo group, or a phosphoric acid group. Examples of the radical polymerizable monomer having an acid group include esters of an aliphatic polyhydroxy compound and an unsaturated carboxylic acid. Examples of commercially available products include M-305, M-510, and M-520 of the Aronix series manufactured by Toagosei Co., Ltd. The acid value of the radical polymerizable monomer having an acid group is preferably 0.1 to 40 mgKOH / g. The lower limit is preferably 5 mgKOH / g or more. The upper limit is preferably 30 mgKOH / g or less.

[0152] The cationic polymerizable monomer may be a compound having a cationic polymerizable group. The cationic polymerizable group may be a cyclic ether group such as an epoxy group or an oxetanyl group. The cationic polymerizable monomer is preferably a compound having a cyclic ether group, more preferably a compound having an epoxy group (also called an epoxy compound).

[0153] The molecular weight of the cationic polymerizable monomer is preferably 200 to 3000. The upper limit of the molecular weight is preferably 2500 or less, more preferably 2000 or less. The lower limit of the molecular weight is preferably 250 or more, more preferably 300 or more.

[0154] The epoxy compound may be a compound having one or more epoxy groups in one molecule, and preferably a compound having two or more epoxy groups. The epoxy group is preferably 1 to 100 in one molecule. The upper limit of the epoxy group may be, for example, 10 or less, or 5 or less. The lower limit of the epoxy group is preferably 2 or more.

[0155] The epoxy compound includes a compound represented by the following formula (EP1). [ka]

[0156] In formula (EP1), R EP1 ~R EP3 R each independently represents a hydrogen atom, a halogen atom, or an alkyl group. The alkyl group may have a cyclic structure and may have a substituent. EP1 and R EP2 , R EP2 and R EP3 may be bonded to each other to form a ring structure. EP is a single bond or n EP R represents an organic group having a valence of 1. EP1 ~R EP3 Q EP may be bonded to form a ring structure. EP represents an integer of 2 or more, preferably 2 to 10, and more preferably 2 to 6. EP If is a single bond, n EP is 2. R EP1 ~R EP3 , Q EPFor details, see paragraphs 0087 to 0088 of JP 2014-089408 A, the contents of which are incorporated herein by reference. Specific examples of the compound represented by formula (EP1) include the compound described in paragraph 0090 of JP 2014-089408 A and the compound described in paragraph 0151 of JP 2010-054632 A, the contents of which are incorporated herein by reference.

[0157] As the cationic polymerizable monomer, commercially available products can be used, such as the Adeka Glycirol series manufactured by ADEKA CORPORATION (e.g., Adeka Glycirol ED-505, etc.) and the Epolead series manufactured by Daicel Corporation (e.g., Epolead GT401, etc.).

[0158] The content of the polymerizable monomer is preferably 0.1 to 40% by mass based on the total solid content of the composition. The lower limit is preferably 0.5% by mass or more, more preferably 1% by mass or more. The upper limit is preferably 30% by mass or less, more preferably 20% by mass or less. The polymerizable monomer may be used alone or in combination of two or more. When two or more polymerizable monomers are used in combination, the total amount is preferably within the above range. When two or more polymerizable monomers are used in combination, two or more radical polymerizable monomers may be used alone, or a radical polymerizable monomer and a cationic polymerizable monomer may be used in combination.

[0159] The total content of the polymerizable monomer and the resin is preferably 10 to 90% by mass based on the total solid content of the composition. The upper limit is preferably 80% by mass or less, and more preferably 75% by mass or less. The lower limit is preferably 20% by mass or more, and more preferably 30% by mass or more.

[0160] The ratio of the polymerizable monomer to the resin is preferably 10 to 400 parts by mass of the polymerizable monomer per 100 parts by mass of the resin. The lower limit is preferably 15 parts by mass or more, more preferably 20 parts by mass or more. The upper limit is preferably 380 parts by mass or less, more preferably 350 parts by mass or less.

[0161] <<Solvent>> The composition of the present invention contains a solvent. Examples of the solvent include organic solvents. Basically, the solvent is not particularly limited as long as it satisfies the solubility of each component and the coatability of the composition. Examples of the organic solvent include ester-based solvents, ketone-based solvents, alcohol-based solvents, amide-based solvents, ether-based solvents, and hydrocarbon-based solvents. For details of these, the description in paragraph number 0223 of International Publication No. 2015 / 166779 can be referred to, and the contents of this specification are incorporated herein. In addition, ester-based solvents substituted with a cyclic alkyl group and ketone-based solvents substituted with a cyclic alkyl group can also be preferably used. Specific examples of organic solvents include acetone, methyl ethyl ketone, cyclohexane, cyclohexanone, cyclopentanone, ethyl acetate, butyl acetate, cyclohexyl acetate, ethylene dichloride, tetrahydrofuran, toluene, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol dimethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, acetylacetone, diacetone alcohol, ethylene glycol monomethyl ether acetate, ethylene glycol ethyl ether acetate, ethylene glycol monoisopropyl ether, and ethylene glycol monobutyl ether acetate. Examples of the organic solvent include dimethyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, 3-methoxypropyl acetate, N,N-dimethylformamide, dimethylsulfoxide, γ-butyrolactone, methyl lactate, ethyl lactate, butyl diglycol acetate, 3-methoxybutyl acetate, 3-methoxy-N,N-dimethylpropanamide, and 3-butoxy-N,N-dimethylpropanamide. These organic solvents can be used alone or in combination.

[0162] In the present invention, it is preferable to use an organic solvent with a low metal content, and the metal content of the organic solvent is preferably 10 mass ppb (parts per billion) or less. If necessary, an organic solvent with a mass ppt (parts per trillion) level may be used, and such an organic solvent is provided, for example, by Toyo Gosei Co., Ltd. (The Chemical Daily, November 13, 2015).

[0163] Methods for removing impurities such as metals from organic solvents include, for example, distillation (molecular distillation, thin film distillation, etc.) and filtration using a filter. The filter used for filtration has a filter pore size of preferably 10 μm or less, more preferably 5 μm or less, and even more preferably 3 μm or less. The filter material is preferably polytetrafluoroethylene, polyethylene, or nylon.

[0164] The organic solvent may contain isomers (compounds having the same number of atoms but different structures). In addition, the organic solvent may contain only one type of isomer or multiple types of isomers.

[0165] The content of peroxide in the organic solvent is preferably 0.8 mmol / L or less, and more preferably contains substantially no peroxide.

[0166] The content of the solvent in the composition is preferably 10 to 95% by mass. The lower limit is preferably 20% by mass or more, more preferably 30% by mass or more, and even more preferably 40% by mass or more. The upper limit is preferably 90% by mass or less, more preferably 85% by mass or less, and even more preferably 80% by mass or less. Only one type of solvent may be used, or two or more types may be used in combination. When two or more types of solvents are used in combination, the total of the solvents is preferably within the above range.

[0167] <<Photopolymerization initiator>> The composition of the present invention may contain a photopolymerization initiator. Examples of the photopolymerization initiator include a photoradical polymerization initiator and a photocationic polymerization initiator. It is preferable to select and use the photopolymerization initiator according to the type of polymerizable monomer. When a radical polymerizable monomer is used as the polymerizable monomer, it is preferable to use a photoradical polymerization initiator as the photopolymerization initiator. Also, when a cationic polymerizable monomer is used as the polymerizable monomer, it is preferable to use a photocationic polymerization initiator as the photopolymerization initiator. The photopolymerization initiator is not particularly limited and can be appropriately selected from known photopolymerization initiators. For example, a compound having photosensitivity to light rays in the ultraviolet to visible regions is preferable.

[0168] The content of the photopolymerization initiator is preferably 0.1 to 50 mass% of the total solid content of the composition, more preferably 0.5 to 30 mass%, and even more preferably 1 to 20 mass%. The composition of the present invention may contain only one type of photopolymerization initiator, or may contain two or more types. When two or more types of photopolymerization initiators are contained, the total amount thereof is preferably within the above range.

[0169] (Photoradical polymerization initiator) Examples of the photoradical polymerization initiator include halogenated hydrocarbon derivatives (e.g., compounds having a triazine skeleton, compounds having an oxadiazole skeleton, etc.), acylphosphine compounds, hexaarylbiimidazole, oxime compounds, organic peroxides, thio compounds, ketone compounds, aromatic onium salts, α-hydroxyketone compounds, α-aminoketone compounds, etc. From the viewpoint of exposure sensitivity, the photopolymerization initiator is preferably a trihalomethyltriazine compound, a benzyldimethylketal compound, an α-hydroxyketone compound, an α-aminoketone compound, an acylphosphine compound, a phosphine oxide compound, a metallocene compound, an oxime compound, a triarylimidazole dimer, an onium compound, a benzothiazole compound, a benzophenone compound, an acetophenone compound, a cyclopentadiene-benzene-iron complex, a halomethyloxadiazole compound, and a 3-aryl-substituted coumarin compound, more preferably a compound selected from an oxime compound, an α-hydroxyketone compound, an α-aminoketone compound, and an acylphosphine compound, and even more preferably an oxime compound. Examples of the photopolymerization initiator include compounds described in paragraphs 0065 to 0111 of JP2014-130173A and Japanese Patent No. 6301489, the contents of which are incorporated herein by reference.

[0170] Commercially available α-hydroxyketone compounds include Omnirad 184, Omnirad 1173, Omnirad 2959, Omnirad 127 (manufactured by IGM Resins BV), Irgacure 184, Irgacure 1173, Irgacure 2959, Irgacure 127 (manufactured by BASF), etc. Commercially available α-aminoketone compounds include Omnirad 907, Omnirad 369, Omnirad 369E, Omnirad 379EG (manufactured by IGM Resins BV), Irgacure 907, Irgacure 369, Irgacure 369E, Irgacure 379EG (manufactured by BASF), etc. Commercially available acylphosphine compounds include Omnirad 819, Omnirad TPO (both manufactured by IGM Resins BV), Irgacure 819, Irgacure TPO (both manufactured by BASF), and the like.

[0171] Examples of the oxime compound include compounds described in JP-A-2001-233842, compounds described in JP-A-2000-080068, compounds described in JP-A-2006-342166, compounds described in J.C.S. Perkin II (1979, pp. 1653-1660), compounds described in J.C.S. Perkin II (1979, pp. 156-162), compounds described in Journal of Photopolymer Science and Technology (1995, pp. 202-232), compounds described in JP 2000-066385 A, compounds described in JP 2000-080068 A, compounds described in JP-T-2004-534797 A, compounds described in JP 2006-342166 A, compounds described in JP 2017-019766 A, compounds described in Japanese Patent No. 6065596, compounds described in WO 2015 / 152153, compounds described in WO 2017 / 051680, compounds described in JP 2017-198865 A, compounds described in paragraphs 0025 to 0038 of WO 2017 / 164127, compounds described in WO 2013 / 167515, and the like. Specific examples of the oxime compound include 3-benzoyloxyiminobutan-2-one, 3-acetoxyiminobutan-2-one, 3-propionyloxyiminobutan-2-one, 2-acetoxyiminopentan-3-one, 2-acetoxyimino-1-phenylpropan-1-one, 2-benzoyloxyimino-1-phenylpropan-1-one, 3-(4-toluenesulfonyloxy)iminobutan-2-one, and 2-ethoxycarbonyloxyimino-1-phenylpropan-1-one. Examples of commercially available products include Irgacure OXE01, Irgacure OXE02, Irgacure OXE03, and Irgacure OXE04 (all manufactured by BASF), TR-PBG-304 (manufactured by Changzhou Strong Electronic New Materials Co., Ltd.), and Adeka Optomer N-1919 (manufactured by ADEKA Corporation, photopolymerization initiator 2 described in JP 2012-014052 A). In addition, it is also preferable to use, as the oxime compound, a compound that is not colorable or a compound that is highly transparent and does not easily discolor.Commercially available products include ADEKA Arcles NCI-730, NCI-831, and NCI-930 (all manufactured by ADEKA Corporation).

[0172] As the photopolymerization initiator, an oxime compound having a fluorene ring can also be used. Specific examples of the oxime compound having a fluorene ring include the compounds described in JP2014-137466A.

[0173] As the photopolymerization initiator, an oxime compound having a skeleton in which at least one benzene ring of a carbazole ring is replaced with a naphthalene ring can also be used. Specific examples of such oxime compounds include the compounds described in WO 2013 / 083505.

[0174] As the photopolymerization initiator, an oxime compound having a fluorine atom can also be used. Specific examples of the oxime compound having a fluorine atom include the compounds described in JP-A-2010-262028, compounds 24, 36 to 40 described in JP-T-2014-500852, and compound (C-3) described in JP-A-2013-164471.

[0175] As the photopolymerization initiator, an oxime compound having a nitro group can be used. It is also preferable that the oxime compound having a nitro group is a dimer. Specific examples of the oxime compound having a nitro group include the compounds described in paragraphs 0031 to 0047 of JP 2013-114249 A, paragraphs 0008 to 0012, and 0070 to 0079 of JP 2014-137466 A, the compounds described in paragraphs 0007 to 0025 of Japanese Patent No. 4223071 A, and Adeka Arcles NCI-831 (manufactured by ADEKA Corporation).

[0176] As the photopolymerization initiator, an oxime compound having a benzofuran skeleton can also be used. Specific examples include OE-01 to OE-75 described in WO 2015 / 036910.

[0177] Specific examples of oxime compounds that can be preferably used in the present invention are shown below, but the present invention is not limited to these.

[0178] [ka] [ka]

[0179] The oxime compound is preferably a compound having a maximum absorption wavelength in the wavelength range of 350 to 500 nm, more preferably a compound having a maximum absorption wavelength in the wavelength range of 360 to 480 nm. In addition, the molar absorption coefficient of the oxime compound at a wavelength of 365 nm or 405 nm is preferably high from the viewpoint of sensitivity, more preferably 1000 to 300000, even more preferably 2000 to 300000, and particularly preferably 5000 to 200000. The molar absorption coefficient of the compound can be measured using a known method. For example, it is preferable to measure using ethyl acetate at a concentration of 0.01 g / L using a spectrophotometer (Varian Cary-5 spectrophotometer).

[0180] As the photopolymerization initiator, a bifunctional or trifunctional or higher functional photoradical polymerization initiator may be used. By using such a photoradical polymerization initiator, two or more radicals are generated from one molecule of the photoradical polymerization initiator, so that good sensitivity can be obtained. In addition, when a compound having an asymmetric structure is used, the crystallinity is reduced and the solubility in a solvent or the like is improved, so that precipitation is less likely to occur over time, and the stability over time of the coloring composition can be improved. Specific examples of bifunctional or trifunctional or higher functional photoradical polymerization initiators include dimers of oxime compounds described in JP-T-2010-527339, JP-T-2011-524436, WO-P-2015 / 004565, WO-P-2016-532675, paragraphs 0407 to 0412, and WO-P-2017 / 033680, paragraphs 0039 to 0055, and compounds described in JP-T-2013-522445. Examples of the photoinitiator include the compound (E) and the compound (G), Cmpd1 to 7 described in International Publication No. 2016 / 034963, the oxime ester photoinitiator described in paragraph 0007 of JP-T2017-523465, the photoinitiator described in paragraphs 0020 to 0033 of JP-A2017-167399, and the photopolymerization initiator (A) described in paragraphs 0017 to 0026 of JP-A2017-151342.

[0181] The content of the photoradical polymerization initiator is preferably 0.1 to 50 mass % of the total solid content of the composition, more preferably 0.5 to 30 mass %, and even more preferably 1 to 20 mass %. The composition of the present invention may contain only one type of photoradical polymerization initiator, or may contain two or more types. When two or more types of photoradical polymerization initiators are contained, the total amount thereof is preferably within the above range.

[0182] (Photocationic polymerization initiator) The photo-cationic polymerization initiator may be a photo-acid generator, which may be an onium salt compound such as a diazonium salt, a phosphonium salt, a sulfonium salt, or an iodonium salt, which is decomposed by irradiation with light to generate an acid, or a sulfonate compound such as an imide sulfonate, an oxime sulfonate, a diazodisulfone, a disulfone, or an o-nitrobenzyl sulfonate.

[0183] Examples of the photocationic polymerization initiator include compounds represented by the following formulas (b1), (b2), and (b3). [ka]

[0184] In the above formula, R 201 ~R 207 Each of R independently represents an organic group. The number of carbon atoms in the organic group is preferably 1 to 30. Examples of the organic group include an alkyl group and an aryl group. In formula (b1), R 201 ~R 203 Two of the X may be bonded to form a ring structure, and the ring may contain an oxygen atom, a sulfur atom, an ester bond, an amide bond, or a carbonyl group. - represents a non-nucleophilic anion. Examples of the non-nucleophilic anion include a sulfonate anion, a carboxylate anion, a bis(alkylsulfonyl)amide anion, a tris(alkylsulfonyl)methide anion, and BF 4 - , P.F. 6 - , SbF 6 - For details of the compounds represented by formulae (b1), (b2) and (b3), reference can be made to paragraphs 0139 to 0214 of JP-A No. 2009-258603, the contents of which are incorporated herein by reference.

[0185] Specific examples of the photocationic polymerization initiator include compounds having the following structures: [ka]

[0186] The cationic photopolymerization initiator may be a commercially available product. Examples of commercially available cationic photopolymerization initiators include ADEKA ARCLES SP series (for example, ADEKA ARCLES SP-606, etc.) manufactured by ADEKA CORPORATION, and IRGACURE250, IRGACURE270, and IRGACURE290 manufactured by BASF Corporation.

[0187] The content of the cationic photopolymerization initiator is preferably 0.1 to 50 mass% of the total solid content of the composition, more preferably 0.5 to 30 mass%, and even more preferably 1 to 20 mass%. The composition of the present invention may contain only one type of cationic photopolymerization initiator, or may contain two or more types. When two or more types of cationic photopolymerization initiators are contained, the total amount thereof is preferably within the above range.

[0188] <<Pigment derivatives>> The composition of the present invention may further contain a pigment derivative. Examples of the pigment derivative include compounds having a structure in which a portion of the chromophore is substituted with an acidic group, a basic group, or a phthalimidomethyl group. Examples of the acidic group include a sulfo group, a carboxyl group, and its quaternary ammonium salt group. Examples of the basic group include an amino group. For details of the pigment derivative, refer to paragraphs 0162 to 0183 of JP-A-2011-252065, the contents of which are incorporated herein by reference. The content of the pigment derivative is preferably 1 to 30 parts by mass, more preferably 3 to 20 parts by mass, relative to 100 parts by mass of the pigment. Only one type of pigment derivative may be used, or two or more types may be used in combination. When two or more types of pigment derivatives are used in combination, the total amount of the pigment derivatives is preferably within the above range.

[0189] <<Coloring prevention agent>> The composition of the present invention may contain a coloring inhibitor. The coloring inhibitor described in this specification can also be used as a polymerization inhibitor. Examples of the coloring inhibitor include phenol compounds, phosphite compounds, and thioether compounds, and more preferably, phenol compounds having a molecular weight of 500 or more, phosphite compounds having a molecular weight of 500 or more, or thioether compounds having a molecular weight of 500 or more. In addition, the coloring inhibitor is preferably a phenol compound, and more preferably, a phenol compound having a molecular weight of 500 or more.

[0190] As the phenolic compound, any phenolic compound known as a phenolic coloring inhibitor can be used. A preferred phenolic compound is a hindered phenolic compound. In particular, a compound having a substituent at the site (ortho position) adjacent to the phenolic hydroxyl group is preferred. The aforementioned substituent is preferably a substituted or unsubstituted alkyl group having 1 to 22 carbon atoms. Also preferred is a compound having a phenolic group and a phosphite ester group in the same molecule.

[0191] As the phenolic hydroxyl group-containing compound, particularly polysubstituted phenol compounds are preferably used. There are three types of polysubstituted phenol compounds (hindered type of formula (A), semi-hindered type of formula (B), and less hindered type of formula (C)) with different substitution positions and structures based on the reactivity to the peroxy radical captured by the stable phenoxy radical generation. [ka] In the formulae (A) to (C), R is a hydrogen atom or a substituent. R is preferably a hydrogen atom, a halogen atom, an amino group which may have a substituent, an alkyl group which may have a substituent, an aryl group which may have a substituent, an alkoxy group which may have a substituent, an aryloxy group which may have a substituent, an alkylamino group which may have a substituent, an arylamino group which may have a substituent, an alkylsulfonyl group which may have a substituent, or an arylsulfonyl group which may have a substituent, and more preferably an amino group which may have a substituent, an alkyl group which may have a substituent, an aryl group which may have a substituent, an alkoxy group which may have a substituent, an aryloxy group which may have a substituent, an alkylamino group which may have a substituent, or an arylamino group which may have a substituent.

[0192] More preferred is a composite coloring inhibitor in which a plurality of structures that exhibit the coloring prevention function represented by the above formulas (A) to (C) are present in the same molecule, and specifically, a compound in which 2 to 4 structures that exhibit the coloring prevention function represented by the above formulas (A) to (C) are present in the same molecule is preferred. Among these, the semi-hindered type represented by formula (B) is more preferred from the viewpoint of coloring properties. Representative examples available as commercially available products include (A) Sumilizer BHT (manufactured by Sumitomo Chemical Co., Ltd.), Irganox 1010, 1222 (manufactured by BASF), Adeka STAB AO-20, AO-50, AO-60 (manufactured by ADEKA Corporation), etc.; (B) Sumilizer BBM-S (manufactured by Sumitomo Chemical Co., Ltd.), Irganox 245 (manufactured by BASF), Adeka STAB AO-80 (manufactured by ADEKA Corporation), etc.; (C) Adeka STAB AO-30, AO-40 (manufactured by ADEKA Corporation), etc.

[0193] Examples of the phosphite ester compound include tris[2-[[2,4,8,10-tetrakis(1,1-dimethylethyl)dibenzo[d,f][1,3,2]dioxaphosphepin-6-yl]oxy]ethyl]amine, tris[2-[(4,6,9,11-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphepin-2-yl)oxy]ethyl]amine, and ethyl bis(2,4-di-tert-butyl-6-methylphenyl)phosphite. A representative example of a commercially available phosphite ester compound is Adeka STAB PEP-36A (manufactured by ADEKA Corporation).

[0194] Examples of thioether compounds include dialkyl thiodipropionates such as dilauryl thiodipropionate, dimyristyl thiodipropionate, and distearyl thiodipropionate, as well as pentaerythritol tetra(β-alkylthiopropionic acid) esters; pentaerythrityl tetrakis(3-laurylthiopropionate); tetrakis[methylene-3-(laurylthio)propionate]methane, bis(methyl-4-[3-n-alkyl(C12 / C14)thio ... pionyloxy]5-t-butylphenyl)sulfide, ditridecyl-3,3'-thiodipropionate, dilauryl-3,3'-thiodipropionate, dimyristyl-3,3'-thiodipropionate, distearyl-3,3'-thiodipropionate, lauryl / stearyl thiodipropionate, 4,4'-thiobis(6-t-butyl-metacresol), 2,2'-thiobis(6-t-butyl-paracresol), distearyl disulfide, and the like. Representative examples of commercially available thioether compounds include ADK STAB AO-412S (CAS: 29598-76-3, manufactured by ADEKA CORPORATION), ADK STAB AO-503 (CAS: 10595-72-9, manufactured by ADEKA CORPORATION), and KEMINOX PLS (CAS: 29598-76-3, manufactured by Chemipro Chemical Co., Ltd.).

[0195] In addition to the representative examples mentioned above, commercially available color inhibitors include ADK STAB AO-50F, ADK STAB AO-60G, and ADK STAB AO-330 (ADEKA CORPORATION).

[0196] In addition, the coloring inhibitor is N-oxide compounds such as 5,5-dimethyl-1-pyrroline N-oxide, 4-methylmorpholine N-oxide, pyridine N-oxide, 4-nitropyridine N-oxide, 3-hydroxypyridine N-oxide, picolinic acid N-oxide, nicotinic acid N-oxide, and isonicotinic acid N-oxide; piperidine-1-oxyl free radical compounds such as piperidine-1-oxyl free radical, 2,2,6,6-tetramethylpiperidine-1-oxyl free radical, 4-oxo-2,2,6,6-tetramethylpiperidine-1-oxyl free radical, 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl free radical, 4-acetamido-2,2,6,6-tetramethylpiperidine-1-oxyl free radical, 4-maleimido-2,2,6,6-tetramethylpiperidine-1-oxyl free radical, and 4-phosphonooxy-2,2,6,6-tetramethylpiperidine-1-oxyl free radical; Pyrrolidine 1-oxyl free radical compounds such as 3-carboxyproxyl free radical and 3-carboxy-2,2,5,5-tetramethylpyrrolidine 1-oxyl free radical; N-nitrosophenylhydroxyamines such as N-nitrosophenylhydroxyamine cerous salt and N-nitrosophenylhydroxyamine aluminum salt; diazonium compounds such as 4-diazophenyldimethylamine hydrogen sulfate, 4-diazodiphenylamine tetrafluoroborate, and 3-methoxy-4-diazodiphenylamine hexafluorophosphate; Cationic dyes; Nitro-containing compounds; FeCl 3 , CuCl 2It is also possible to use transition metal compounds such as those mentioned above. For details of these compounds, mention may be made of the compounds described in paragraphs 0211 to 0223 of JP-A-2015-034961, the contents of which are incorporated herein by reference.

[0197] The content of the coloring inhibitor is preferably 0.01 to 20 mass% of the total solid content of the composition from the viewpoint of coloring property and solvent resistance, more preferably 0.1 to 15 mass%, and particularly preferably 0.3 to 5 mass%. Only one type of coloring inhibitor may be used, or two or more types may be used in combination. When two or more types are used in combination, the total amount thereof is preferably within the above range.

[0198] <<Ultraviolet absorbing agent>> The composition of the present invention may contain an ultraviolet absorber. Examples of ultraviolet absorbers include conjugated diene compounds, aminobutadiene compounds, methyldibenzoyl compounds, coumarin compounds, salicylate compounds, benzophenone compounds, benzotriazole compounds, acrylonitrile compounds, and hydroxyphenyltriazine compounds. For details of ultraviolet absorbers, refer to paragraphs 0052-0072 of JP2012-208374A and paragraphs 0317-0334 of JP2013-068814A, the contents of which are incorporated herein by reference. Examples of commercially available conjugated diene compounds include UV-503 (manufactured by Daito Chemical Co., Ltd.). In addition, MYUA series (The Chemical Daily, February 1, 2016) manufactured by Miyoshi Oil and Fat may be used as the benzotriazole compound.

[0199] The content of the ultraviolet absorber is preferably 0.1 to 10% by mass, more preferably 0.1 to 7% by mass, even more preferably 0.1 to 5% by mass, and particularly preferably 0.1 to 3% by mass, based on the total solid content of the composition, from the viewpoints of pattern shape and solvent resistance. Only one type of ultraviolet absorber may be used, or two or more types may be used in combination. When two or more types are used in combination, the total amount thereof is preferably within the above range.

[0200] <<Adhesive>> The composition of the present invention may contain an adhesive. There is no particular limitation on the adhesive, and any known adhesive can be used. Examples of the adhesive include a silane coupling agent.

[0201] In this specification, the silane coupling agent means a silane compound having a hydrolyzable group and other functional groups. The hydrolyzable group means a substituent that is directly bonded to a silicon atom and can generate a siloxane bond by at least one of a hydrolysis reaction and a condensation reaction. Examples of the hydrolyzable group include a halogen atom, an alkoxy group, and an acyloxy group, and an alkoxy group is preferred. That is, the silane coupling agent is preferably a compound having an alkoxysilyl group. Examples of functional groups other than the hydrolyzable group include a vinyl group, a (meth)allyl group, a (meth)acryloyl group, a mercapto group, an epoxy group, an oxetanyl group, an amino group, a ureido group, a sulfide group, an isocyanate group, and a phenyl group, and an amino group, a (meth)acryloyl group, and an epoxy group are preferred. Specific examples of the silane coupling agent include N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane (Shin-Etsu Chemical Co., Ltd., trade name KBM-602), N-β-aminoethyl-γ-aminopropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., trade name KBM-603), N-β-aminoethyl-γ-aminopropyltriethoxysilane (Shin-Etsu Chemical Co., Ltd., trade name KBE-602), γ-aminopropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., trade name KBM-903), γ-aminopropyltriethoxysilane (Shin-Etsu Chemical Co., Ltd., trade name KBE-903), 3-methacryloxypropylmethyldimethoxysilane (Shin-Etsu Chemical Co., Ltd., trade name KBM-502), and 3-methacryloxypropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., trade name KBM-503). Specific examples of the silane coupling agent include the compounds described in paragraphs 0018 to 0036 of JP-A No. 2009-288703 and the compounds described in paragraphs 0056 to 0066 of JP-A No. 2009-242604, the contents of which are incorporated herein by reference.

[0202] The content of the adhesive agent is preferably 0.01 to 10 mass % of the total solid content of the composition, more preferably 0.1 to 7 mass %, particularly preferably 1 to 5 mass %. Only one type of adhesive agent may be used, or two or more types may be used in combination. When two or more types are used in combination, the total amount thereof is preferably within the above range.

[0203] <<Polymerization inhibitor>> The composition of the present invention may contain a polymerization inhibitor. Examples of the polymerization inhibitor include hydroquinone, p-methoxyphenol, di-tert-butyl-p-cresol, pyrogallol, tert-butylcatechol, 1,4-benzoquinone, 4,4'-thiobis(3-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-methyl-6-t-butylphenol), and N-nitrosophenylhydroxyamine salts (ammonium salts, cerous salts, etc.). Among these, p-methoxyphenol is preferred. The content of the polymerization inhibitor is preferably 0.0001 to 5% by mass based on the total solid content of the composition.

[0204] <<Chain transfer agent>> The composition of the present invention may contain a chain transfer agent. Examples of the chain transfer agent include N,N-dialkylaminobenzoic acid alkyl esters and thiol compounds, and thiol compounds are preferred. The thiol compound is preferably a compound having two or more (preferably 2 to 8, more preferably 3 to 6) mercapto groups in the molecule. Specific examples of the thiol compound include thiol compounds having a heterocycle such as 2-mercaptobenzothiazole, 2-mercaptobenzoxazole, 2-mercaptobenzimidazole, N-phenylmercaptobenzimidazole, 1,3,5-tris(3-mercaptobutyloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, and aliphatic thiol compounds such as pentaerythritol tetrakis(3-mercaptobutyrate) and 1,4-bis(3-mercaptobutyryloxy)butane. In addition, examples of commercially available chain transfer agents include PEMP (manufactured by SC Organic Chemical Industry Co., Ltd., a thiol compound), Suncerer M (manufactured by Sanshin Chemical Industry Co., Ltd., a thiol compound), and Karenz MT BD1 (manufactured by Showa Denko K.K., a thiol compound). In addition, it is also preferable to use a compound having the following structure. [ka]

[0205] The content of the chain transfer agent is preferably 0.2 to 5.0% by mass, more preferably 0.4 to 3.0% by mass, based on the total solid content of the composition. The content of the chain transfer agent is preferably 1 to 40 parts by mass, more preferably 2 to 20 parts by mass, based on 100 parts by mass of the polymerizable monomer. Only one type of chain transfer agent may be used, or two or more types may be used in combination. When two or more types are used in combination, the total amount thereof is preferably within the above range.

[0206] <<Sensitizer>> The composition of the present invention may contain a sensitizer for the purpose of improving the radical generation efficiency of the photopolymerization initiator and increasing the photosensitive wavelength. The sensitizer is preferably one that sensitizes the photopolymerization initiator by an electron transfer mechanism or an energy transfer mechanism. The sensitizer may be a compound having an absorption in the range of 300 to 450 nm. For details of the sensitizer, refer to the description in paragraphs 0231 to 0253 of JP 2010-106268 A (corresponding to paragraphs 0256 to 0273 of the specification of US Patent Application Publication No. 2011 / 0124824), the contents of which are incorporated herein by reference.

[0207] The content of the sensitizer is preferably 0.1 to 20 mass % of the total solid content of the composition, more preferably 0.5 to 15 mass %. The sensitizer may be used alone or in combination of two or more. When two or more types are used in combination, the total amount thereof is preferably within the above range.

[0208] <<Cosensitizer>> The composition of the present invention preferably further contains a co-sensitizer. The co-sensitizer has the effect of further improving the sensitivity of the photopolymerization initiator or sensitizer to actinic radiation, or suppressing the polymerization inhibition of the polymerizable monomer caused by oxygen. For the co-sensitizer, the description in paragraphs 0254 to 0257 of JP 2010-106268 A (corresponding paragraphs 0277 to 0279 of the specification of US Patent Application Publication No. 2011 / 0124824) can be referred to, and the contents thereof are incorporated herein by reference.

[0209] The content of the co-sensitizer is preferably 0.1 to 30% by mass, more preferably 1 to 25% by mass, and even more preferably 1.5 to 20% by mass, based on the total solid content of the composition. Only one type of co-sensitizer may be used, or two or more types may be used in combination. When two or more types are used in combination, the total amount thereof is preferably within the above range.

[0210] <<Surfactants>> The composition of the present invention may contain various types of surfactants from the viewpoint of further improving the coating suitability. As the surfactant, various types of surfactants such as fluorine-based surfactants, nonionic surfactants, cationic surfactants, anionic surfactants, and silicone-based surfactants can be used.

[0211] By including a fluorosurfactant in the composition of the present invention, the liquid properties (particularly, fluidity) when prepared as a coating liquid are further improved, and the uniformity of the coating thickness and the liquid saving can be further improved. That is, when a film is formed using a coating liquid to which a composition containing a fluorosurfactant is applied, the interfacial tension between the surface to be coated and the coating liquid is reduced, the wettability to the surface to be coated is improved, and the suitability for application to the surface to be coated is improved. Therefore, a film of uniform thickness with little thickness unevenness can be more suitably formed.

[0212] The fluorine content in the fluorosurfactant is preferably 3 to 40 mass%, more preferably 5 to 30 mass%, and particularly preferably 7 to 25 mass%. A fluorosurfactant having a fluorine content within this range is effective in terms of uniformity of the coating film thickness and liquid saving properties, and also has good solubility in the composition.

[0213] Examples of fluorine-based surfactants include those described in JP2014-041318A, paragraphs 0060 to 0064 (corresponding to WO2014 / 017669, paragraphs 0060 to 0064) and those described in JP2011-132503A, paragraphs 0117 to 0132, the contents of which are incorporated herein by reference. Commercially available fluorine-based surfactants include, for example, Megafac F171, F172, F173, F176, F177, F141, F142, F143, F144, R30, F437, F475, F479, F482, F554, F780, EXP, and MFS-330 (all manufactured by DIC Corporation), Fluorad FC430, FC431, and FC171 (all manufactured by Sumitomo 3M Limited), Surflon S-382, SC-101, SC-103, SC-104, SC-105, SC-1068, SC-381, SC-383, S-393, and KH-40 (all manufactured by Asahi Glass Co., Ltd.), and PolyFox. Examples include PF636, PF656, PF6320, PF6520, PF7002 (all manufactured by OMNOVA), and Ftergent FTX218 (manufactured by Neos).

[0214] In addition, the fluorosurfactant may be an acrylic compound that has a molecular structure with a functional group containing a fluorine atom, and when heat is applied, the functional group containing the fluorine atom is broken and the fluorine atom volatilizes. Examples of such fluorosurfactants include the Megafac DS series manufactured by DIC Corporation (The Chemical Daily (February 22, 2016), Nikkei Business Daily (February 23, 2016)), such as Megafac DS-21.

[0215] In addition, it is also preferable to use a polymer of a fluorine atom-containing vinyl ether compound having a fluorinated alkyl group or a fluorinated alkylene ether group and a hydrophilic vinyl ether compound as the fluorine-based surfactant. Examples of such a fluorine-based surfactant include the fluorine-based surfactants described in JP 2016-216602 A, the contents of which are incorporated herein by reference.

[0216] The fluorosurfactant may be a block polymer. The fluorosurfactant may be a fluorine-containing polymer compound that contains a repeating unit derived from a (meth)acrylate compound having a fluorine atom and a repeating unit derived from a (meth)acrylate compound having two or more (preferably five or more) alkyleneoxy groups (preferably ethyleneoxy groups, propyleneoxy groups). In addition, the fluorine-containing surfactants described in paragraphs 0016 to 0037 of JP-A-2010-032698 and the following compounds are also exemplified as the fluorosurfactant used in the present invention. [ka] The weight average molecular weight of the above compound is preferably 3,000 to 50,000, for example, 14,000. In the above compound, % indicating the proportion of repeating units is mol %.

[0217] In addition, the fluorine-based surfactant may be a fluorine-containing polymer having an ethylenically unsaturated bond-containing group in a side chain.Specific examples include the compounds described in paragraphs 0050 to 0090 and 0289 to 0295 of JP 2010-164965 A, and Megafac RS-101, RS-102, RS-718K, and RS-72-K manufactured by DIC Corporation.In addition, the fluorine-based surfactant may be the compounds described in paragraphs 0015 to 0158 of JP 2015-117327 A.

[0218] Examples of silicone surfactants include Toray Silicone DC3PA, Toray Silicone SH7PA, Toray Silicone DC11PA, Toray Silicone SH21PA, Toray Silicone SH28PA, Toray Silicone SH29PA, Toray Silicone SH30PA, Toray Silicone SH8400 (all manufactured by Toray Dow Corning Co., Ltd.), TSF-4440, TSF-4300, TSF-4445, TSF-4460, TSF-4452 (all manufactured by Momentive Performance Materials, Inc.), KP341, KF6001, KF6002 (all manufactured by Shin-Etsu Silicone Co., Ltd.), BYK307, BYK323, BYK330 (all manufactured by BYK-Chemie).

[0219] The content of the surfactant is preferably 0.001 to 2.0% by mass, more preferably 0.005 to 1.0% by mass, based on the total solid content of the composition. Only one type of surfactant may be used, or two or more types may be used in combination. When two or more types are used in combination, the total amount thereof is preferably within the above range.

[0220] <<Other additives>> Furthermore, known additives such as plasticizers and oil sensitizers may be added to the composition to improve the physical properties of the film. Examples of plasticizers include dioctyl phthalate, didodecyl phthalate, triethylene glycol dicaprylate, dimethyl glycol phthalate, tricresyl phosphate, dioctyl adipate, dibutyl sebacate, and triacetyl glycerin. The content of the plasticizer is preferably 10% by mass or less based on the total amount of the above-mentioned compound (1), the polymerizable monomer, and the resin.

[0221] <Containment Container> The container for storing the composition of the present invention is not particularly limited, and a known container can be used. In addition, it is also preferable to use a multi-layer bottle whose inner wall is made of six types of six-layer resin or a bottle with a seven-layer structure made of six types of resin as the container, in order to suppress the incorporation of impurities into the raw materials or the composition. Examples of such containers include the container described in JP-A-2015-123351. In addition, it is also preferable that the inner wall of the container is made of glass or stainless steel in order to prevent metal elution from the inner wall of the container, increase the storage stability of the composition, and suppress the deterioration of the components.

[0222] <Method of preparing the composition> The composition of the present invention can be prepared by mixing the above-mentioned components. When preparing the composition, each component may be mixed at once, or each component may be dissolved or dispersed in a solvent and then mixed successively. In addition, there is no particular restriction on the order of addition and working conditions when mixing. In addition, the preparation of the composition preferably includes a process for dispersing particles. In the process for dispersing particles, the mechanical force used for dispersing the particles includes compression, squeezing, impact, shear, cavitation, etc. Specific examples of these processes include a bead mill, a sand mill, a roll mill, a ball mill, a paint shaker, a microfluidizer, a high-speed impeller, a sand grinder, a flow jet mixer, high-pressure wet atomization, ultrasonic dispersion, etc. In addition, in the grinding of particles in a sand mill (bead mill), it is preferable to use beads with a small diameter, increase the filling rate of beads, etc., and perform the treatment under conditions that increase the grinding efficiency. In addition, it is preferable to remove coarse particles by filtration, centrifugation, etc. after the grinding treatment. In addition, the process and dispersing machine for dispersing particles can be suitably used as described in "Dispersion Technology Encyclopedia, published by Information Technology Co., Ltd., July 15, 2005" or "Dispersion Technology and Industrial Applications Focused on Suspension (Solid / Liquid Dispersion System) Comprehensive Data Collection, published by Management Development Center Publishing Department, October 10, 1978" and JP2015-157893A, paragraph number 0022. In addition, in the process for dispersing particles, a salt milling process may be used to perform a particle refinement process. The materials, equipment, processing conditions, etc. used in the salt milling process can be referred to, for example, JP2015-194521A and JP2012-046629A.

[0223] In preparing the composition, it is preferable to filter the composition with a filter for the purpose of removing foreign matter and reducing defects. Any filter that has been used for filtering purposes can be used without any particular limitation. For example, filters using materials such as fluororesins such as polytetrafluoroethylene (PTFE), polyamide resins such as nylon (e.g., nylon-6, nylon-6,6), and polyolefin resins (including high-density and ultra-high-molecular-weight polyolefin resins) such as polyethylene and polypropylene (PP) can be used. Among these materials, polypropylene (including high-density polypropylene) and nylon are preferable.

[0224] The pore size of the filter is preferably 0.01 to 10.0 μm, more preferably 0.05 to 3.0 μm, and even more preferably about 0.1 to 2.0 μm. The nominal value of the filter manufacturer can be referred to for the pore size value of the filter. Various filters provided by Nippon Pall Corporation (DFA4201NIEY, etc.), Advantech Toyo Co., Ltd., Nippon Integris Co., Ltd. (formerly Nippon Microlith Co., Ltd.), Kitz Microfilter Co., Ltd., etc. can be used.

[0225] It is also preferable to use a fibrous filter medium as the filter. Examples of fibrous filter medium include polypropylene fiber, nylon fiber, glass fiber, etc. Commercially available products include SBP type series (SBP008, etc.), TPR type series (TPR002, TPR005, etc.), and SHPX type series (SHPX003, etc.) manufactured by ROKI TECHNO CO., LTD.

[0226] When using a filter, different filters (for example, a first filter and a second filter, etc.) may be combined. In this case, filtration with each filter may be performed only once or two or more times. Filters having different pore sizes within the above-mentioned range may be combined. Filtration with the first filter may be performed only on the dispersion liquid, and filtration with the second filter may be performed after mixing with other components.

[0227] <Membrane> The first aspect of the film of the present invention is a film obtained by using the composition of the present invention described above. The film of the first aspect has a maximum transmittance of light in the wavelength range of 400 to 700 nm of preferably 80% or less, more preferably 70% or less, even more preferably 60% or less, and particularly preferably 50% or less. The lower limit of the maximum transmittance is preferably 1% or more, more preferably 5% or more, and even more preferably 10% or more.

[0228] A second aspect of the film of the present invention is a film comprising particles having a refractive index of 2.0 or more and an average primary particle size of 200 nm or less, and a film-forming component comprising at least one selected from a resin and a polymerizable monomer, or a cured product derived from the film-forming component, The maximum transmittance of light in the wavelength range of 400 to 700 nm is 80% or less, The film-forming component includes two or more resins, or includes one or more resins and one or more polymerizable monomers; The film has a phase separation structure of a first phase containing the particles and a second phase having a lower content of the particles than the first phase. The particles and film-forming components contained in the film of the second embodiment include the materials described in the section on the composition of the present invention above, and the preferred ranges are also the same.

[0229] In the film of the second embodiment, the phase separation structure is preferably a sea-island structure or a bicontinuous phase structure. By forming these phase separation structures, light can be effectively scattered between the first phase and the second phase, and particularly excellent light scattering properties are easily obtained. In the sea-island structure, the second phase may be a sea and the first phase may form islands, or the first phase may be a sea and the second phase may form islands. When the first phase is a sea and the second phase forms islands, it is preferable from the viewpoint of transmittance. When the first phase is an island and the second phase forms a sea, it is preferable from the viewpoint of angle dependency.

[0230] The film of the second aspect has a maximum transmittance of light in the wavelength range of 400 to 700 nm of preferably 80% or less, more preferably 70% or less, even more preferably 60% or less, and particularly preferably 50% or less. The lower limit of the maximum transmittance is preferably 1% or more, more preferably 5% or more, and even more preferably 10% or more.

[0231] The maximum light transmittance of the films of the first and second aspects of the present invention (hereinafter also simply referred to as the film of the present invention) at 400 to 1000 nm is preferably 80% or less, more preferably 60% or less, and even more preferably 50% or less. The lower limit of the maximum light transmittance is preferably 1% or more, more preferably 5% or more, and even more preferably 10% or more.

[0232] The haze of the film of the present invention based on JIS K 7136 is preferably 30 to 100%. The upper limit is preferably 99% or less, more preferably 95% or less, and even more preferably 90% or less. The lower limit is preferably 35% or more, more preferably 40% or more, and even more preferably 50% or more. The haze of the film is a value measured by the method described in the examples described later.

[0233] The L* value of the film of the present invention in the CIE1976 L*a*b* color system is preferably 35 to 100. The L* value is preferably 40 or more, more preferably 50 or more, and even more preferably 60 or more. According to this embodiment, a film having excellent whiteness can be obtained. Moreover, the L* value is preferably 95 or less, more preferably 90 or less, and even more preferably 85 or less. According to this embodiment, a film having appropriate visible transparency can be obtained.

[0234] The a* value is preferably -15 or more, more preferably -10 or more, and even more preferably -5 or more. The a* value is preferably 10 or less, more preferably 5 or less, and even more preferably 0 or less. According to this embodiment, a film having excellent whiteness can be obtained.

[0235] The value of b* is preferably −35 or more, more preferably −30 or more, and even more preferably −25 or more. The value of b* is preferably 20 or less, more preferably 10 or less, and even more preferably 0 or less. According to this embodiment, a film having excellent whiteness can be obtained.

[0236] The thickness of the film of the present invention is preferably 2 to 40 μm. The upper limit of the film thickness is preferably 30 μm or less, more preferably 20 μm or less, and even more preferably 15 μm or less. The lower limit of the film thickness is preferably 3 μm or more, more preferably 4 μm or more, and even more preferably 5 μm or more. If the film thickness is within the above range, the effect of thinning the sensor and improving the optical sensitivity of the device by suppressing crosstalk can be expected.

[0237] The film of the present invention can be suitably used as a scattering layer for a light-emitting device, a scattering layer for a display device, and the like.

[0238] <Membrane manufacturing method> The film of the present invention can be produced through a process of applying the composition of the present invention onto a support. Examples of the support include substrates made of materials such as silicon, alkali-free glass, soda glass, Pyrex (registered trademark) glass, and quartz glass. An organic film or an inorganic film may be formed on these substrates. Examples of materials for the organic film include resins. Substrates made of resins may also be used as the support. A charge-coupled device (CCD), a complementary metal oxide semiconductor (CMOS), a transparent conductive film, and the like may be formed on the support. A black matrix for isolating each pixel may also be formed on the support. If necessary, an undercoat layer may be provided on the support to improve adhesion with the upper layer, prevent diffusion of substances, or flatten the surface of the substrate. When a glass substrate is used as the support, it is preferable to form an inorganic film on the glass substrate or to subject the glass substrate to a dealkali treatment before use.

[0239] The composition can be applied to a support by a known method, such as a dropping method (drop casting), a slit coating method, a spray method, a roll coating method, a spin coating method, a casting coating method, a slit and spin method, a pre-wetting method (for example, a method described in JP-A-2009-145395), various printing methods such as ejection printing such as inkjet (for example, on-demand method, piezo method, thermal method), nozzle jet, flexographic printing, screen printing, gravure printing, reverse offset printing, and metal mask printing, a transfer method using a mold, and a nanoimprint method. The application method by inkjet is not particularly limited, and examples thereof include the method described in the patent publications shown in "Expanding and Usable Inkjet - Infinite Possibilities Seen in Patents -, published in February 2005 by Sumibe Techno Research" (particularly pages 115 to 133), and the methods described in JP-A No. 2003-262716, JP-A No. 2003-185831, JP-A No. 2003-261827, JP-A No. 2012-126830, and JP-A No. 2006-169325. In terms of coating suitability, the coating by spin coating is preferably performed at a speed of 300 to 6000 rpm, and more preferably at a speed of 400 to 3000 rpm. In addition, the temperature of the support during spin coating is preferably 10 to 100°C, and more preferably 20 to 70°C. If the temperature is within the above range, a film with excellent coating uniformity can be easily produced. In the case of the dropping method (drop casting), it is preferable to form a dropping area of ​​the composition with a partition of the photoresist on the support so that a uniform film with a predetermined film thickness can be obtained. The desired film thickness can be obtained by controlling the dropping amount and solid content concentration of the composition and the area of ​​the dropping area.

[0240] The composition layer formed on the support may be dried (prebaked) under the prebaking conditions, for example, preferably at a temperature of 60 to 150° C. for 30 seconds to 15 minutes.

[0241] The film manufacturing method may further include a step of forming a pattern. The pattern forming method may include a pattern forming method using a photolithography method and a pattern forming method using a dry etching method. When the film of the present invention is used as a flat film, the step of forming a pattern may not be performed. The step of forming a pattern will be described in detail below.

[0242] (When forming patterns using photolithography) The pattern forming method by photolithography preferably includes a step of exposing the composition layer formed by applying the composition of the present invention to light in a pattern (exposure step), and a step of developing the composition layer by removing the unexposed portion to form a pattern (development step). If necessary, a step of baking the developed pattern (post-baking step) may be provided. Each step will be described below.

[0243] <<Exposure process>> In the exposure step, the composition layer is exposed in a pattern. For example, the composition layer can be exposed to light through a mask having a predetermined mask pattern using an exposure device such as a stepper, thereby allowing the composition layer to be pattern-exposed. This allows the exposed portion to be cured. Examples of radiation (light) that can be used for exposure include g-rays and i-rays. Light with a wavelength of 300 nm or less (preferably light with a wavelength of 180 to 300 nm) can also be used. Examples of light with a wavelength of 300 nm or less include KrF rays (wavelength 248 nm) and ArF rays (wavelength 193 nm), with KrF rays (wavelength 248 nm) being preferred.

[0244] In addition, during exposure, light may be continuously irradiated or may be irradiated in pulses (pulse exposure). Pulse exposure is an exposure method in which light irradiation and pauses are repeated in a short cycle (for example, millisecond level or less). In the case of pulse exposure, the pulse width is preferably 100 nanoseconds (ns) or less, more preferably 50 nanoseconds or less, and even more preferably 30 nanoseconds or less. There is no particular limit to the lower limit of the pulse width, but it can be 1 femtosecond (fs) or more, and can also be 10 femtoseconds or more. The frequency is preferably 1 kHz or more, more preferably 2 kHz or more, and even more preferably 4 kHz or more. The upper limit of the frequency is preferably 50 kHz or less, more preferably 20 kHz or less, and even more preferably 10 kHz or less. The maximum instantaneous illuminance is 50,000,000 W / m 2 It is preferable that the power consumption is 100,000,000 W / m or more. 2 More preferably, it is 200,000,000 W / m or more. 2 It is more preferable that the upper limit of the maximum instantaneous illuminance is 1000000000 W / m 2 Preferably, it is less than 800,000,000 W / m 2 More preferably, it is 500,000,000 W / m or less. 2 It is more preferable that the pulse width is equal to or less than 1000 s. The pulse width refers to the time during which light is irradiated in a pulse period. The frequency refers to the number of pulse periods per second. The maximum instantaneous irradiance refers to the average irradiance during the time during which light is irradiated in a pulse period. The pulse period refers to a period in which light irradiation and pause in pulse exposure constitute one cycle.

[0245] The irradiation amount (exposure amount) is, for example, 0.03 to 2.5 J / cm 2 is preferable, and 0.05 to 1.0 J / cm 2 More preferably, 0.08 to 0.5 J / cm 2is most preferable. The oxygen concentration during exposure can be appropriately selected. For example, exposure may be performed in the air, in a low-oxygen atmosphere with an oxygen concentration of 19 volume% or less (e.g., 15 volume%, 5 volume%, substantially oxygen-free), or in a high-oxygen atmosphere with an oxygen concentration of more than 21 volume% (e.g., 22 volume%, 30 volume%, 50 volume%). The exposure illuminance can be appropriately set, and is preferably 1000 to 100000 W / m 2 The oxygen concentration and exposure illuminance may be appropriately combined. For example, the oxygen concentration is 10% by volume and the illuminance is 10,000 W / m 2 , oxygen concentration 35% by volume, illuminance 20000W / m 2 etc.

[0246] <<Developing process>> Next, the composition layer in the unexposed portion of the composition layer after exposure is developed and removed to form a pattern. The composition layer in the unexposed portion can be developed and removed using a developer. As a result, the composition layer in the unexposed portion in the exposure step is dissolved into the developer, and only the photocured portion remains on the support. The temperature of the developer is preferably, for example, 20 to 30°C. The development time is preferably 20 to 180 seconds. In addition, in order to improve the removability of residues, the process of shaking off the developer every 60 seconds and supplying new developer may be repeated several times.

[0247] Examples of the developer include organic solvents and alkaline developers, and alkaline developers are preferably used. As the alkaline developer, an alkaline aqueous solution (alkaline developer) obtained by diluting an alkaline agent with pure water is preferred. Examples of the alkaline agent include organic alkaline compounds such as ammonia, ethylamine, diethylamine, dimethylethanolamine, diglycolamine, diethanolamine, hydroxylamine, ethylenediamine, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, ethyltrimethylammonium hydroxide, benzyltrimethylammonium hydroxide, dimethylbis(2-hydroxyethyl)ammonium hydroxide, choline, pyrrole, piperidine, and 1,8-diazabicyclo[5.4.0]-7-undecene, and inorganic alkaline compounds such as sodium hydroxide, potassium hydroxide, sodium carbonate, sodium hydrogencarbonate, sodium silicate, and sodium metasilicate. As the alkaline agent, compounds with a large molecular weight are preferred in terms of the environment and safety. The concentration of the alkaline agent in the alkaline aqueous solution is preferably 0.001 to 10% by mass, more preferably 0.01 to 1% by mass. The developer may further contain a surfactant. Examples of the surfactant include the surfactants described above, and nonionic surfactants are preferred. The developer may be produced as a concentrated solution from the viewpoint of convenience of transportation and storage, and then diluted to a required concentration when used. The dilution ratio is not particularly limited, but can be set in the range of, for example, 1.5 to 100 times. When an alkaline aqueous solution is used as the developer, it is preferred to wash (rinse) with pure water after development. It is also preferred to rinse by supplying a rinsing liquid to the developed composition layer while rotating the support on which the developed composition layer is formed. It is also preferred to move the nozzle for ejecting the rinsing liquid from the center of the support to the periphery of the support. In this case, the nozzle may be moved while gradually decreasing the moving speed when moving the nozzle from the center of the support to the periphery. By performing rinsing in this manner, it is possible to suppress in-plane variation in rinsing.The same effect can also be obtained by gradually decreasing the rotation speed of the support while moving the nozzle from the center to the periphery of the support.

[0248] After development and drying, it is preferable to perform additional exposure treatment or heating treatment (post-baking). Additional exposure treatment and post-baking are curing treatments after development to complete curing. The heating temperature in post-baking is preferably, for example, 100 to 260°C. The lower limit of the heating temperature is preferably 120°C or more, more preferably 160°C or more. The upper limit of the heating temperature is preferably 240°C or less, more preferably 220°C or less. Post-baking can be performed in a continuous or batch manner using a heating means such as a hot plate, a convection oven (hot air circulation dryer), or a high-frequency heater so that the developed film meets the above conditions. When additional exposure treatment is performed, the light used for exposure is preferably light with a wavelength of 400 nm or less. The additional exposure treatment may be performed by the method described in Korean Patent Publication No. 10-2017-0122130.

[0249] (When forming patterns using dry etching) The pattern formation by the dry etching method can be performed by applying the composition of the present invention onto a support, curing the composition layer formed to form a cured layer, forming a patterned resist layer on the cured layer, and then dry etching the cured layer using the patterned resist layer as a mask and an etching gas. For the pattern formation by the dry etching method, the description in paragraphs 0010 to 0067 of JP 2013-064993 A can be referred to, and the contents thereof are incorporated herein.

[0250] <Optical sensor> The optical sensor of the present invention has the film of the present invention. The types of optical sensors include an ambient light sensor and an illuminance sensor, and are preferably used as an ambient light sensor. An ambient light sensor is a sensor that detects the color tone of the surrounding light (ambient light).

[0251] In addition to the film of the present invention, the optical sensor of the present invention preferably has an optical filter having at least one pixel selected from color pixels and pixels of an infrared transmission filter. Examples of the color pixels include red pixels, blue pixels, green pixels, yellow pixels, cyan pixels, and magenta pixels. In addition, the film of the present invention is preferably provided on the light incident side of the optical filter. By providing the film of the present invention on the light incident side of the optical filter, the angle dependency of each pixel can be further reduced.

[0252] An embodiment of the optical sensor is shown with reference to the drawings. The optical sensor 1 shown in FIG. 1 includes an optical filter 110 having pixels 111-114 on a photoelectric conversion element 101. A film 121 of the present invention is formed on the optical filter 110. An example of the pixels 111-114 constituting the optical filter 110 is a combination in which the pixel 111 is a red pixel, the pixel 112 is a blue pixel, the pixel 113 is a green pixel, and the pixel 114 is an infrared transmission filter pixel. In the optical sensor 1 shown in FIG. 1, the optical filter 110 has four types of pixels (pixels 111-114), but the types of pixels may be one to three types, or five or more types. It can be appropriately selected according to the application. A planarization layer may be interposed between the photoelectric conversion element 101 and the optical filter 110, or between the optical filter 110 and the film 121 of the present invention.

[0253] FIG. 2 shows another embodiment of the optical sensor. In the optical sensor 2 shown in FIG. 2, an optical filter 110 having pixels 111 to 114 is provided on a photoelectric conversion element 101. The optical filter 110 has the same configuration as the above-mentioned embodiment. A member having a film 122 of the present invention formed on the surface of a transparent support 130 is disposed on the optical filter 110. Examples of the transparent support 130 include a glass substrate and a resin substrate. In the optical sensor 2 shown in FIG. 2, a member having a film 122 of the present invention formed on the surface of the transparent support 130 is disposed on the optical filter 110 at a predetermined interval, but the optical filter 110 and the member having a film 122 of the present invention formed on the surface of the transparent support 130 may be in contact with each other. In the optical sensor 2 shown in FIG. 2, the film 122 of the present invention is formed only on one side of the transparent support 130, but the film 122 of the present invention may be formed on both sides of the transparent support 130. 2, the film 122 of the present invention is formed on the surface of the transparent support 130 facing the optical filter 110, but the film 122 of the present invention may be formed on the surface of the transparent support 130 opposite to the optical filter 110. A planarizing layer may be interposed between the photoelectric conversion element 101 and the optical filter 110, or between the film 122 of the present invention and the transparent support 130. EXAMPLES

[0254] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0255] <Measurement of the average primary particle size> The primary particle diameter of the particles was determined by observing the particles under a transmission electron microscope (TEM) and observing the non-aggregated portions of the particles (primary particles). Specifically, the primary particles were photographed using a transmission electron microscope, and the photograph was then used to measure the particle size distribution using an image processing device. The average primary particle diameter of the particles was determined as the arithmetic mean diameter based on the number calculated from the particle size distribution. A Hitachi electron microscope (H-7000) was used as the transmission electron microscope, and a Luzex AP made by Nireco Corporation was used as the image processing device.

[0256] <Measurement of refractive index of particles> A dispersion liquid was prepared using particles, a resin (dispersant) with a known refractive index, and propylene glycol monomethyl ether acetate. The prepared dispersion liquid was then mixed with a resin with a known refractive index to prepare coating liquids with particle concentrations of 10 mass%, 20 mass%, 30 mass%, and 40 mass% in the total solid content of the coating liquid. These coating liquids were formed into films with a thickness of 300 nm on a silicon wafer, and the refractive index of the obtained film was measured using ellipsometry (Lambda Ace RE-3300, manufactured by SCREEN Holdings Co., Ltd.). The particle concentration and refractive index were then plotted on a graph to derive the refractive index of the particles.

[0257] <Measurement of particle specific gravity> 50g of particles were placed in a 100mL measuring flask. Next, 100mL of water was measured using another 100mL measuring cylinder. After that, the measured water was added to the measuring flask so that the particles were immersed, and then ultrasonic waves were applied to the measuring flask to mix the particles with the water. After that, additional water was added until it reached the mark on the measuring flask, and the specific gravity was calculated as 50g / (volume of water remaining in the measuring flask) = specific gravity.

[0258] <Measurement of weight average molecular weight> The weight average molecular weights of the dispersant and resin were measured by gel permeation chromatography (GPC) according to the following conditions. Column type: TOSOH TSKgel Super HZM-H, TOSOH TSKgel Super HZ4000, and TOSOH TSKgel Super HZ2000 connected together Developing solvent: Tetrahydrofuran Column temperature: 40℃ Flow rate (sample injection volume): 1.0 μL (sample concentration 0.1% by mass) Device name: Tosoh Corporation HLC-8220GPC Detector: RI (refractive index) detector Calibration curve base resin: polystyrene resin

[0259] <Polymerizable Group Value> The polymerizable group value of the resin was calculated from the raw materials used in the synthesis of the resin.

[0260] <Acid value measurement method> The acid value represents the mass of potassium hydroxide required to neutralize the acidic components per 1 g of solid content. The measurement sample was dissolved in a mixed solvent of tetrahydrofuran / water = 9 / 1, and the obtained solution was neutralized and titrated with a 0.1 mol / L aqueous sodium hydroxide solution at 25 ° C. using a potentiometric titrator (product name: AT-510, manufactured by Kyoto Electronics Manufacturing Co., Ltd.). The inflection point of the titration pH curve was set as the titration end point, and the acid value was calculated by the following formula. A=56.11×Vs×0.5×f / w A: Acid value (mgKOH / g) Vs: Amount of 0.1 mol / L sodium hydroxide solution required for titration (mL) f: Potency of 0.1 mol / L sodium hydroxide solution w: Measurement sample mass (g) (solid content equivalent)

[0261] <Production of Dispersion> The mixture having the composition shown in the table below was subjected to the following dispersion treatment using an Ultra Apex Mill manufactured by Kotobuki Industries Co., Ltd. as a circulation type dispersion device (bead mill) to produce a dispersion. Bead diameter: 0.2 mm Bead filling rate: 65% by volume Circumferential speed: 6m / sec Pump supply: 10.8kg / hour Cooling water: Tap water Bead mill annular passage internal volume: 0.15L Amount of mixture to be dispersed: 0.65kg

[0262] [Table 1]

[0263] The raw materials listed in the above table are as follows: (particle) [Table 2]

[0264] The refractive index values ​​in the above table are those for light with a wavelength of 589 nm.

[0265] (Resin (dispersant)) B-1: Resin having the following structure (a resin having a structure in which a hexavalent linking group (group Z) is bonded to a polymer chain containing a substituent and a repeating unit of a poly(meth)acrylic structure. Weight average molecular weight: 10,000, acid value: 80.4 mgKOH / g, polymerizable group value: 0 mmol / g) [ka] B-2: Resin having the following structure (a resin containing a repeating unit having a graft chain containing a repeating unit of a polyester structure. The number attached to the main chain indicates the molar ratio of the repeating unit, and the number attached to the side chain indicates the number of repeating units. Weight average molecular weight: 34,000, acid value: 57.2 mg KOH / g, polymerizable group value: 0 mmol / g) [ka] B-5: Resin having the following structure (a resin having a structure in which a hexavalent linking group (group Z) is bonded to a polymer chain containing a substituent and a repeating unit of a poly(meth)acrylic structure. Weight average molecular weight: 6000, acid value: 31 mgKOH / g, polymerizable group value: 1 mmol / g) [ka]

[0266] (solvent) S-1: Propylene glycol monomethyl ether acetate (PGMEA) S-2: Propylene glycol monomethyl ether (PGME) S-3: Cyclohexanone

[0267] <Preparation of Composition> The raw materials shown in the table below were mixed to prepare a composition. [Table 3] [Table 4] [Table 5] [Table 6] [Table 7] [Table 8]

[0268] The raw materials listed in the above table are as follows: (dispersion) Dispersions 1 to 16: Dispersions 1 to 16 described above

[0269] (Polymerizable monomer) M-1: KAYARAD DPHA (manufactured by Nippon Kayaku Co., Ltd., dipentaerythritol hexa(meth)acrylate) M-2: KAYARAD RP-1040 (manufactured by Nippon Kayaku Co., Ltd.) M-3: NK Ester A-TMMT (Shin-Nakamura Chemical Co., Ltd.) M-4: Light Acrylate DCP-A (Kyoeisha Chemical Co., Ltd., dimethylol-tricyclodecane diacrylate)

[0270] (Resin (binder resin)) B-1, B-2, B-5: Resins B-1, B-2, B-5 ​​described above B-3: Resin having the following structure (a resin containing a repeating unit having a graft chain containing a repeating unit of a polyester structure. The number attached to the main chain indicates the molar ratio of the repeating unit, and the number attached to the side chain indicates the number of repeating units. Weight average molecular weight: 20,000, acid value: 49 mg KOH / g, polymerizable group value: 0 mmol / g) [ka] B-4: Resin having the following structure (a resin containing a repeating unit having a graft chain containing a repeating unit of a polyester structure. The number attached to the main chain indicates the molar ratio of the repeating unit, and the number attached to the side chain indicates the number of repeating units. Weight average molecular weight: 20,000, acid value: 75 mgKOH / g, polymerizable group value: 0 mmol / g) [ka] B-6: Resin with the following structure (the numbers attached to the main chain indicate the molar ratio of repeating units. Weight average molecular weight: 11,000, acid value: 69 mg KOH / g, polymerizable group value: 1.4 mmol / g) [ka] B-7: Resin having the following structure (a resin containing a repeating unit having a graft chain containing a repeating unit of a polyester structure. The number attached to the main chain indicates the molar ratio of the repeating unit, and the number attached to the side chain indicates the number of repeating units. Weight average molecular weight: 27500, acid value: 58 mgKOH / g, polymerizable group value: 0 mmol / g) [ka] B-8: Resin having the following structure (a resin containing a repeating unit having a graft chain containing a repeating unit of a polyester structure. The number attached to the main chain indicates the molar ratio of the repeating unit, and the number attached to the side chain indicates the number of repeating units. Weight average molecular weight: 28600, acid value: 61 mgKOH / g, polymerizable group value: 0 mmol / g) [ka] B-9: Resin having the following structure (a resin containing a repeating unit having a graft chain containing a repeating unit of a polyester structure. The number attached to the main chain indicates the molar ratio of the repeating unit, and the number attached to the side chain indicates the number of repeating units. Weight average molecular weight: 23,800, acid value: 59 mg KOH / g, polymerizable group value: 0 mmol / g) [ka] B-10: Resin having the following structure (a resin containing a repeating unit having a graft chain containing a repeating unit of a polyester structure. The number attached to the main chain indicates the molar ratio of the repeating unit, and the number attached to the side chain indicates the number of repeating units. Weight average molecular weight: 25300, acid value: 62 mgKOH / g, polymerizable group value: 0 mmol / g) [ka] B-11: Resin having the following structure (a resin containing a repeating unit having a graft chain containing a repeating unit of a polyester structure. The number attached to the main chain indicates the molar ratio of the repeating unit, and the number attached to the side chain indicates the number of repeating units. Weight average molecular weight: 27700, acid value: 58 mgKOH / g, polymerizable group value: 0 mmol / g) [ka] B-12: Resin having the following structure (a resin containing a repeating unit having a graft chain containing a repeating unit of a polyester structure. The number attached to the main chain indicates the molar ratio of the repeating unit, and the number attached to the side chain indicates the number of repeating units. Weight average molecular weight: 27900, acid value: 58 mgKOH / g, polymerizable group value: 0 mmol / g) [ka] B-13: Resin having the following structure (a resin containing a repeating unit having a graft chain containing a repeating unit of a polyester structure. The number attached to the main chain indicates the molar ratio of the repeating unit, and the number attached to the side chain indicates the number of repeating units. Weight average molecular weight: 29,000, acid value: 57 mg KOH / g, polymerizable group value: 0 mmol / g) [ka] B-14: Resin having the following structure (a resin containing a repeating unit having a graft chain containing a repeating unit of a polyester structure. The number attached to the main chain indicates the molar ratio of the repeating unit, and the number attached to the side chain indicates the number of repeating units. Weight average molecular weight: 30100, acid value: 60 mgKOH / g, polymerizable group value: 0 mmol / g) [ka] B-15: Resin having the following structure (a resin containing a repeating unit having a graft chain containing a repeating unit of a polyester structure. The number attached to the main chain indicates the molar ratio of the repeating unit, and the number attached to the side chain indicates the number of repeating units. Weight average molecular weight: 25300, acid value: 57 mgKOH / g, polymerizable group value: 0 mmol / g) [ka] B-16: Resin having the following structure (a resin containing a repeating unit having a graft chain containing a repeating unit of a polyester structure. The number attached to the main chain indicates the molar ratio of the repeating unit, and the number attached to the side chain indicates the number of repeating units. Weight average molecular weight: 25900, acid value: 61 mgKOH / g, polymerizable group value: 0 mmol / g) [ka] B-17: Resin having the following structure (a resin containing a repeating unit having a graft chain containing a repeating unit of a polyester structure. The number attached to the main chain indicates the molar ratio of the repeating unit, and the number attached to the side chain indicates the number of repeating units. Weight average molecular weight: 30900, acid value: 58 mgKOH / g, polymerizable group value: 0 mmol / g) [ka] B-18: Resin having the following structure (a resin containing a repeating unit having a graft chain containing a repeating unit of a polyester structure. The number attached to the main chain indicates the molar ratio of the repeating unit, and the number attached to the side chain indicates the number of repeating units. Weight average molecular weight: 32500, acid value: 59 mgKOH / g, polymerizable group value: 0 mmol / g) [ka]

[0271] (Photopolymerization initiator) I-1: Irgacure OXE01 (BASF) I-2: Omnirad 369 (manufactured by IGM Resins BV) I-3: Omnirad TPO (IGM Resins BV)

[0272] (Additives) A-1: Adeka STAB AO-80 (ADEKA Corporation, color prevention agent) A-2: Irganox 1010 (BASF, color inhibitor) A-3: KBM-502 (Shin-Etsu Chemical Co., Ltd., silane coupling agent)

[0273] (Surfactant) Su-1: The following compound (% indicating the proportion of repeating units is mol %. Weight average molecular weight: 14,000) [ka] Su-2: Futergent FTX218 (manufactured by Neos)

[0274] (Polymerization inhibitor) In-1: p-Methoxyphenol In-2: 1,4-benzoquinone

[0275] (solvent) S-1: Propylene glycol monomethyl ether acetate (PGMEA) S-2: Propylene glycol monomethyl ether (PGME) S-3: Cyclohexanone

[0276] <Maximum transmittance> Each composition was applied using a spin coater onto an 8-inch (=203.2 mm) glass wafer with an undercoat layer (manufactured by Fujifilm Electronic Materials Co., Ltd., CT-4000L, thickness 0.1 μm) so that the thickness after post-baking would be 4 μm, and heat treatment (pre-baking) was performed for 30 minutes using a hot plate at 110° C. Next, light with a wavelength of 365 nm was applied at 1000 mJ / cm using an i-line stepper exposure device FPA-3000i5+ (manufactured by Canon Inc.). 2 After that, a heat treatment (post-baking) was performed for 5 minutes using a hot plate at 200° C. to form a film with a thickness of 4 μm. The transmittance of the obtained film in the range of 400 to 700 nm in wavelength was measured using a spectrophotometer (U-4100 manufactured by Hitachi High-Technologies Corporation), and the maximum transmittance in the aforementioned range was measured. The maximum transmittance was evaluated according to the following criteria. 5: The maximum transmittance is 50% or less. 4: The maximum transmittance is greater than 50% and less than or equal to 60%. 3: The maximum transmittance is greater than 60% and less than or equal to 70%. 2: The maximum transmittance is greater than 70% and less than or equal to 80%. 1: The maximum transmittance is greater than 80%.

[0277] <Light scattering> Each composition was applied using a spin coater onto an 8-inch (=203.2 mm) glass wafer with an undercoat layer (manufactured by Fujifilm Electronic Materials Co., Ltd., CT-4000L, thickness 0.1 μm) so that the thickness after post-baking would be 4 μm, and heat treatment (pre-baking) was performed for 30 minutes using a hot plate at 110° C. Next, light with a wavelength of 365 nm was applied at 1000 mJ / cm using an i-line stepper exposure device FPA-3000i5+ (manufactured by Canon Inc.). 2 After that, a heat treatment (post-baking) was performed for 5 minutes using a hot plate at 200°C to form a film. The haze value Hz of the obtained film was measured using a haze meter (NDH7000, manufactured by Nippon Denshoku Industries Co., Ltd.). A higher haze value Hz means better light scattering properties. The scattering performance was evaluated according to the following criteria. 5: The haze value Hz is 60% or more. 4: The haze value Hz is 40% or more and less than 60%. 3: The haze value Hz is 20% or more and less than 60%. 2: The haze value Hz is 10% or more and less than 20%. 1: The haze value Hz is less than 10%.

[0278] <Phase separation state> Each composition was applied using a spin coater onto an 8-inch (=203.2 mm) glass wafer with an undercoat layer (manufactured by Fujifilm Electronic Materials Co., Ltd., CT-4000L, thickness 0.1 μm) so that the thickness after post-baking would be 4 μm, and heat treatment (pre-baking) was performed for 30 minutes using a hot plate at 110° C. Next, light with a wavelength of 365 nm was applied at 1000 mJ / cm using an i-line stepper exposure device FPA-3000i5+ (manufactured by Canon Inc.). 2 After that, a heat treatment (post-baking) was performed for 5 minutes using a hot plate at 200° C. to form a film. The cross section of the obtained film in the thickness direction was observed (magnification: 10,000 times) using a scanning electron microscope (SEM) (S-4800H, Hitachi High-Technologies Corporation) to check the uneven distribution of the particles and to determine whether phase separation had occurred. A: A phase-separated structure is formed in the film, with a first phase containing particles and a second phase having a smaller particle content than the first phase. B: No phase separation structure is formed.

[0279] <Storage stability> Each composition obtained above was placed in a container with a liquid height of 20 cm and left to stand for 12 months in a refrigerator (4±1° C.). After standing, samples were taken from 1 cm of the liquid from the top and 1 cm of the liquid from the bottom, and each was applied using a spin coater to an 8-inch (=203.2 mm) glass wafer with an undercoat layer (CT-4000L manufactured by FUJIFILM Electronic Materials Co., Ltd.; thickness 0.1 μm) so that the thickness after post-baking was 4 μm, and heat treatment (pre-baking) was performed for 120 seconds using a hot plate at 110° C. Next, an i-line stepper exposure system FPA-3000i5+ (Canon) was used to irradiate the film with light of 365 nm wavelength at 1000 mJ / cm 2 After that, a heat treatment (post-baking) was performed for 5 minutes using a hot plate at 200° C. to form a film. The transmittance of the obtained film at wavelengths of 400 to 700 nm was measured using a spectrophotometer (U-4100 manufactured by Hitachi High-Technologies Corporation). The maximum transmittance (T1) at wavelengths of 400 to 700 nm for the film formed using the liquid 1 cm from the top, and the maximum transmittance (T2) at wavelengths of 400 to 700 nm for the film formed using the liquid 1 cm from the bottom were calculated, and ΔT, which is the difference (T1-T2), was calculated and storage stability was evaluated according to the following criteria. A smaller ΔT indicates better storage stability. 5: ΔT is less than 3%. 4: ΔT is greater than 3% and less than or equal to 5%. 3: ΔT is greater than 5% and less than or equal to 10%. 2: ΔT is greater than 10% and less than or equal to 20%. 1: ΔT is greater than 20% and less than or equal to 100%.

[0280] <Adhesion> Each composition was applied using a spin coater onto an 8-inch (=203.2 mm) glass wafer with an undercoat layer (CT-4000L manufactured by Fujifilm Electronic Materials Co., Ltd.; thickness 0.1 μm) so that the thickness after pre-baking would be 4 μm, and then heat-treated (pre-baked) for 120 seconds using a hot plate at 110°C. Next, using an i-line stepper exposure system FPA-3000i5+ (Canon Corporation), light with a wavelength of 365 nm was exposed through a pattern mask that formed 25 lines with a width of 100 μm and a length of 1000 μm (exposure dose 50 to 1700 mJ / cm 2 )did. Next, the composition layer after exposure was developed using a developing device (Act8 manufactured by Tokyo Electron). A 0.3 mass% aqueous solution of tetramethylammonium hydroxide (TMAH) was used as the developer, and shower development was performed for 60 seconds at 23°C. Thereafter, rinsing was performed with a spin shower using pure water, followed by spin drying, and then heat treatment (post-baking) was performed for 5 minutes using a hot plate at 200°C to obtain a pattern. The difference ΔE (E2-E1) between the minimum exposure E1 required to form a pattern of 100 μm width × 1000 μm length and the minimum exposure E2 required for all the aforementioned patterns to adhere was calculated, and the adhesion was evaluated according to the following criteria. The smaller ΔE means better adhesion. The pattern adhesion and the size of the pattern were observed using an optical microscope (magnification 200 times). 5: ΔE is 100 mJ / cm 2 Exceeds. 4: ΔE is 0 mJ / cm 2 Exceeds 100mJ / cm 2 The following is the result. 3: ΔE is 0 mJ / cm 2 It is. 2:50~1700mJ / cm 2At least one line pattern of 100 μm width×1000 μm length could be formed with this exposure dose, but it was not possible to form all 25 patterns. 1:50~1700mJ / cm 2 With this exposure dose, it was not possible to form a pattern with a width of 100 μm and a length of 1000 μm.

[0281] [Table 9] [Table 10]

[0282] As shown in the above table, the examples were evaluated as excellent in terms of storage stability and light scattering properties. In addition, the light scattering evaluation of Example 1 using resin B-2 and Examples 48 to 53 using resins B-7 to B-12 was 5, but among them, Examples 48 to 53 had a higher haze value Hz than Example 1, and were more excellent in light scattering. Since resins B-7 to B-12 have graft chains of polyester structure consisting of two types of repeating units, their crystallinity is slightly lower than that of resin B-2 having a graft chain of polyester structure consisting of one type of repeating unit. Therefore, it is presumed that the phase separation size in the film can be prevented from becoming excessively large, and the light scattering performance is excellent. In addition, compared to Example 23 and Example 24 using resins B-3 and B-4, Examples 54 to 59 using resins B-13 to B-18 had excellent light scattering properties. Resins B-13 to B-18 have repeating units that do not contain either a graft chain of a polyester structure or an acid group, and therefore have slightly higher compatibility with the dispersion resin than resins B-3 and B-4 that do not have such repeating units. Therefore, it is presumed that the phase separation size in the film can be prevented from becoming excessively large, resulting in excellent light scattering properties. [Explanation of symbols]

[0283] 1, 2: Optical sensor 101: Photoelectric conversion element 111~114: Pixels 110: Optical filter 121, 122: Membrane 130: Transparent support

Claims

1. A composition comprising particles having a refractive index of 2.0 or more and an average primary particle size of 5 nm or more and 100 nm or less, a film-forming component including a resin and a polymerizable monomer, a photopolymerization initiator, a surfactant, and a solvent, the particles are transparent or white particles, The content of the particles is 15 to 70 mass% of the total solid content of the composition, The film-forming component includes a polymerizable monomer that is a 3- to 15-functional (meth)acrylate compound and two or more resins, The resin contained in the film-forming component is The present invention comprises a resin A2-1 having a repeating unit having a graft chain, and a resin A2-2 having a repeating unit having a graft chain that includes a repeating unit having a structure different from that of the graft chain of the resin A2-1, wherein one of the resin A2-1 and the resin A2-2 is a dispersant and the other is a binder, or a resin A1-3 having a structure in which a polymer chain is bonded to a trivalent or higher linking group, and a resin A2-3 having a repeating unit having a graft chain including a repeating unit having a structure different from that of the polymer chain of the resin A1-3, wherein one of the resin A1-3 and the resin A2-3 is a dispersant and the other is a binder, The composition contains 40 to 250 parts by mass of a resin as a binder relative to 100 parts by mass of a resin as a dispersant, a total content of the polymerizable monomer and the resin is 10 to 75 mass% of a total solid content of the composition, and a ratio of the polymerizable monomer to the resin is 10 to 400 mass parts of the polymerizable monomer per 100 mass parts of the resin, The composition was applied onto a glass wafer using a spin coater, and heat-treated for 30 minutes using a hot plate at 110° C., and then irradiated with light having a wavelength of 365 nm at 1000 mJ / cm. 2 and then heat-treated for 5 minutes using a hot plate at 200° C. to form a film having a thickness of 4 μm, the maximum transmittance of the film in the wavelength range of 400 to 700 nm is 80% or less, and the film has a phase-separated structure consisting of a first phase which is a phase of a film-forming component or a cured product derived from the film-forming component and in which the particles are present, and a second phase which is a phase of a film-forming component or a cured product derived from the film-forming component and in which the particle content is smaller than that of the first phase. composition.

2. 2. The composition according to claim 1, wherein the resin contained in the film-forming component includes at least one selected from a resin having a structure in which a polymer chain containing a repeating unit of a polyester structure is bonded to a trivalent or higher linking group and a resin having a repeating unit having a graft chain containing a repeating unit of a polyester structure.

3. The resin contained in the film-forming component includes the resin A1-3 and the resin A2-3, The resin A2-3 is a resin containing a repeating unit having a graft chain containing a repeating unit of a polyester structure, The composition according to claim 1, wherein the resin A1-3 is a resin having a structure represented by formula (SP-1). 【Chemistry 1】 (In the formula, Z 1 represents a (m+n)-valent linking group, Y 1 and Y 2 each independently represents a single bond or a linking group, A 1 represents a group containing a substituent selected from a heterocyclic group, an acid group, a group having a basic nitrogen atom, a urea group, a urethane group, a group having a coordinating oxygen atom, a hydrocarbon group having 4 or more carbon atoms, an alkoxysilyl group, an epoxy group, an isocyanate group, and a hydroxy group; P 1 represents a polymer chain having a repeating unit of a poly(meth)acrylic structure in the main chain, n represents 1 to 20, m represents 1 to 20, and m+n is 3 to 21; n Y's 1 and A 1 may be the same or different, m Y 2 and P 1 may be the same or different.)

4. The composition according to any one of claims 1 to 3, wherein the particles are inorganic particles.

5. The composition according to any one of claims 1 to 4, comprising two or more types of particles.

6. The composition according to any one of claims 1 to 5, wherein the phase-separated structure is a sea-island structure or a bicontinuous phase structure.

7. A film obtained by using the composition according to any one of claims 1 to 6.

8. An optical sensor comprising the film of claim 7.

Citation Information

Patent Citations

  • Polymer compound and method for producing the same, pigment dispersant, pigment dispersing composition, photocurable composition and color filter and method for producing the same

    JP2007277514A

  • Photosensitive composition and gray cured film, gray pixel, and solid-state imaging element using the same

    JP2014111734A

  • Isotropic light scattering sheet, method for manufacturing the same and application thereof

    JP2016161859A

  • Structure and optical sensor

    WO2018180116A1